Curable silicone composition for transfer molding, cured product thereof, and method for producing same

JP7644605B2Active Publication Date: 2025-03-12DOW TORAY CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2020562491
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-27
Filing Date
2019-12-27
Publication Date
2025-03-12
Estimated Expiration
2039-12-27

AI Technical Summary

Benefits of technology

【0017】 本発明のトランスファー成型用硬化性シリコーン組成物は、トランスファー成型における取扱い作業性および硬化特性に優れると共に、成型した硬化物が高温で低モジュラスかつ柔軟で、応力緩和特性に優れるため、基材との一体成型時に成型物の反りや欠陥を生じにく、かつ、成型後の当該硬化物の脱型性に優れる。また、このようなトランスファー成型用硬化性シリコーン組成物は、簡便な混合工程のみで生産することができ、効率よく製造することができる。さらに、本発明により、上記のトランスファー成型用硬化性シリコーン組成物を用いる成型物(ペレットを特に含む)およびその硬化物を提供することができる。さらに、本発明により、上記組成物の硬化物からなる半導体装置用部材、当該硬化物を有する半導体装置、および、硬化物の成型方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644605000001
    Figure 0007644605000001
Patent Text Reader

Abstract

[Problem] To provide a curable silicone composition and its uses, in which the molded, cured product during transfer molding has low modulus and flexibility even at high temperatures, and has excellent stress relaxation properties, making the molded product less likely to warp or have defects, particularly when integrally molded with a substrate, and in which the cured product after transfer molding has excellent demoldability (mold release). [Solution] A curable silicone composition for transfer molding, which (1) has a maximum torque value of less than 50 dN·m, as measured by MDR (Moving Die Rheometr) at molding temperatures from room temperature to 200°C, and (2) has a loss tangent (tanδ) value, expressed as the ratio of stored torque value to lost torque value, of less than 0.2 when the maximum torque value is reached, and uses thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable silicone composition for transfer molding, which can be obtained by a simple production method, and which gives a molded cured product that has low modulus and flexibility even at high temperatures, has excellent stress relaxation properties, and is excellent in transfer moldability and demoldability when using the composition, as well as molded products (pellets, etc.) and cured products thereof. The present invention also relates to a cured product of the composition and its uses (particularly semiconductor members), a production method for the composition, and a molding method for the cured product, etc. [Background technology]

[0002] Curable silicone compositions are used in a wide range of industrial fields because they cure to form cured products that have excellent heat resistance, cold resistance, electrical insulation, weather resistance, water repellency, and transparency. Cured products of such curable silicone compositions generally do not discolor as easily as other organic materials, and the deterioration of physical properties is small, so they are also suitable as optical materials and sealants for semiconductor devices.

[0003] The present applicant has proposed a hot-melt curable granular silicone composition and a reactive silicone composition for molding in Patent Documents 1 and 2. These silicone compositions are made of so-called phenyl silicone resins, and have the advantages of superior hot-melt properties compared to methyl silicone resins, as well as superior hardness and strength of the cured product.

[0004] Meanwhile, in recent years, optical semiconductor devices and the like have become smaller and have higher output, and when these hot-melt curable granular silicone compositions and the like are used, coloring due to the phenyl silicone resin may occur, particularly at high temperatures of 200° C. or higher, and the light reflectance may decrease, particularly in the field of reflective materials. For this reason, there is a strong demand for silicone compositions that achieve hot-melt properties and mechanical strength of the cured product after molding, while also meeting the requirements for higher heat resistance and coloring resistance.

[0005] Here, Patent Document 3 discloses a hot-melt curable silicone sheet using a methyl silicone resin, but the present invention does not describe or suggest a granular composition. Furthermore, an organic solvent is essential in the kneading process of the composition, and no composition or granular composition containing a large amount of functional fillers (especially white pigments) suitable for molding materials is described or suggested. Furthermore, the composition requires removal of the organic solvent in the process of sheet preparation, and only a thin sheet can be prepared to avoid the solvent remaining, making it difficult to use as a composition for molding. In addition, heat is applied in the process of removing the solvent, making it difficult to achieve the fast curing / instant curing properties required in the molding process. For this reason, it was difficult to apply the composition disclosed in Patent Document 3 to solve the above problems.

[0006] Furthermore, Patent Document 4 discloses curable silicone pellets for molding that use a methylsilicone resin. However, the production of this composition requires melt-kneading at high temperatures, making it difficult to control the curability of the composition and difficult to mold at low temperatures in a short time.

[0007] Meanwhile, the present applicants have proposed in Patent Documents 5 to 7 that the use of an inorganic filler that does not contain coarse particles in a curable granular silicone composition can improve toughness and durability, particularly at high temperatures, gap-filling properties when melted, and light reflectance, etc. In addition, Patent Document 8 proposes a curable silicone composition that, by using a hot-melt component such as a metal stearate in combination, has hot-melt properties, can achieve sufficient fluidity and gap-filling properties when heated and melted, has excellent handling properties and adhesive properties of the cured product, and gives a cured product that is excellent in flexibility and toughness from room temperature to high temperatures of about 150°C.

[0008] However, in recent years, in order to meet the demand for application to various semiconductor applications, these curable silicone compositions still have room for improvement in their properties. In particular, in transfer molding, there is generally a trade-off between demoldability and the stress relaxation properties of the cured product, making it difficult to achieve both properties, and the recent trend toward finer mold structures has a tendency to make demoldability even more difficult.

[0009] That is, in the case of a hot-melt silicone composition for molding with a reduced linear expansion coefficient as in Patent Document 4, the resulting cured product is hard during transfer molding, so that a slight difference in the linear expansion coefficient between the substrate and the resulting cured product is likely to cause warping or defects. On the other hand, when a hot-melt curable granular silicone composition with excellent high-temperature softening properties is used for transfer molding, the cured product has a soft property at high temperatures, so that it is difficult to separate from the mold after curing, and the mold release property from the mold having a fine structure may be insufficient. For this reason, there is a strong demand for a curable silicone composition that has excellent stress relaxation properties of the cured product, does not cause warping or defects, and has excellent mold release properties.

[0010] Meanwhile, the present applicant has proposed a thermosetting film-like silicone encapsulant for encapsulating semiconductor elements by compression molding, which has an initial torque value of less than 15 dN·m as measured by MDR at molding temperatures from room temperature to 200°C (Patent Document 9). This encapsulant is useful in that it has excellent moldability for encapsulating semiconductors such as LEDs, does not cause problems such as overflow from a mold, and has no defects such as voids, but it does not achieve both demoldability during transfer molding and stress relaxation properties of the cured product, in particular, prevention of warping of molded products and demoldability, and there is still room for improvement in its performance. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] International Publication No. 2016 / 136243 Brochure [Patent Document 2] JP 2014-009322 A [Patent Document 3] Special Publication No. 2017-512224 [Patent Document 4] JP 2009-155415 A [Patent Document 5] International Publication No. 2018 / 030286 Brochure [Patent Document 6] International Publication No. 2018 / 030287 Brochure [Patent Document 7] International Publication No. 2018 / 030288 Brochure [Patent Document 8] International Patent Application No. PCT / JP2018 / 19574 [Patent Document 9] Patent Publication No. 2013-232580 Summary of the Invention [Problem to be solved by the invention]

[0012] The object of the present invention is to provide a curable silicone composition that is excellent in handling and curing properties in transfer molding, and the molded cured product has low modulus and flexibility even at high temperatures and has excellent stress relaxation properties, so that the molded product is unlikely to warp or have defects when integrally molded with a substrate, and the cured product has excellent demoldability after transfer molding. Another object of the present invention is to provide a molded product (particularly including pellets) using the curable silicone composition and a cured product thereof. Another object of the present invention is to provide a cured product of the composition and its uses (particularly including semiconductor members and power semiconductors having the cured product), a method for producing the composition, and a method for molding the cured product. [Means for solving the problem]

[0013] As a result of extensive investigations, the present inventors have discovered a curable silicone composition for transfer molding that (1) has a maximum torque value of less than 50 dN m, and (2) has a loss tangent (tan δ), expressed as the ratio of stored torque value / loss torque value, of less than 0.2 when the maximum torque value is reached, as measured by a moving die rheometer (MDR) at molding temperatures from room temperature to 200°C. In particular, the present inventors have discovered a curable silicone composition for transfer molding that contains (A) a curable reactive organopolysiloxane, (B) a functional filler, and (C) a curing agent, and in which 50 mass % or more of component (A) has (A1) a curable reactive functional group containing at least one carbon-carbon double bond in the molecule, and 3 / 2 (wherein R is a monovalent organic group) and a siloxane unit represented by SiO 4 / 2 The present invention has been achieved by finding that the above problems can be solved by a curable silicone composition for transfer molding, which is an organopolysiloxane containing at least 20 mol % or more of siloxane units selected from the siloxane units represented by the formula (B), and the content of component (B) is 40 vol % or less of the entire composition. Here, the above curable silicone composition for transfer molding may be in a paste form, but the entire composition is preferably hot-melt. In addition, the above curable silicone composition is preferably in a pellet form.

[0014] Furthermore, the present inventors have discovered that the above problems can be solved by using a cured product of the above-mentioned curable silicone composition for transfer molding, in particular the use of the cured product as a component for a semiconductor device, and by a semiconductor device (including one or more selected from the group consisting of power semiconductor devices, optical semiconductor devices, and semiconductor devices mounted on flexible circuit boards) having the cured product, and have arrived at the present invention.

[0015] Similarly, the inventors have discovered that the above problems can be solved by a production method characterized by granulating only the specific components that make up the above-mentioned curable silicone composition by mixing them at a temperature not exceeding 50°C, and by a method for molding a cured product using the above-mentioned curable granular silicone composition, and have arrived at the present invention.

[0016] The curable silicone composition of the present invention has excellent moldability and demoldability, and is suitable for use as a transfer molding material.Furthermore, the curable silicone composition of the present invention can be used as a molding material for the so-called overmolding method, a process in which a semiconductor element or a semiconductor circuit board is covered by a cured product through overmolding. Effect of the Invention

[0017] The curable silicone composition for transfer molding of the present invention is excellent in handling and curing properties in transfer molding, and the molded cured product has low modulus and flexibility at high temperatures and excellent stress relaxation properties, so that the molded product is unlikely to warp or have defects when integrally molded with a substrate, and the cured product after molding has excellent demoldability. In addition, such a curable silicone composition for transfer molding can be produced by a simple mixing process alone, and can be efficiently manufactured. Furthermore, the present invention can provide a molded product (particularly including pellets) using the above-mentioned curable silicone composition for transfer molding, and a cured product thereof. Furthermore, the present invention can provide a semiconductor device member made of a cured product of the above-mentioned composition, a semiconductor device having the cured product, and a molding method for the cured product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] [Curing behavior of curable silicone composition for transfer molding] The curable silicone composition of the present invention is a curable silicone composition for transfer molding, and the composition as a whole may be in the form of a paste or a molded product such as hot melt pellets. In order to achieve both demoldability in transfer molding and stress relaxation properties of the cured product, which are intrinsically in a trade-off relationship, such a composition must have (1) a maximum torque value of less than 50 dN·m measured by MDR (Moving Die Rheometer) at molding temperatures from room temperature to 200°C, and (2) a loss tangent (tan δ) value expressed as the ratio of stored torque value / loss torque value when the maximum torque value is reached must be less than 0.2. In particular, it is particularly preferable that (1) the maximum torque value measured by MDR set at 150°C, which is a general molding temperature, is less than 50 dN·m, and (2) the loss tangent (tan δ) value expressed as the ratio of stored torque value / loss torque value when the maximum torque value is reached is less than 0.2. Furthermore, it goes without saying that as long as the above-mentioned curing behavior is satisfied and the physical property value of MDR at a specific temperature (e.g., 150°C) is satisfied, the curable silicone composition for transfer molding of the present invention can be used at a desired molding temperature selected as desired from room temperature to 200°C (e.g., a molding temperature other than 150°C).

[0019] The maximum torque value will be described. In the present invention, the torque value is the torque value obtained by measuring the cured product obtained by curing (=vulcanizing) the present composition using an MDR in accordance with JIS K 6300-2 "Unvulcanized rubber - Physical properties - Part 2: Determination of vulcanization properties using a vibration vulcanization tester", and the maximum torque value is the maximum torque value measured for 600 seconds after vulcanization at a molding temperature, preferably at 150°C. Here, the maximum torque value of the cured product at the molding temperature being less than 50 dN·m means that the cured product after molding is soft even at high temperatures, that is, the cured product is low modulus and flexible, has a low elastic modulus, and has excellent stress relaxation properties. In the present invention, the maximum torque value of the cured product at the molding temperature may be less than 40 dN·m, preferably less than 35 dN·m, and particularly preferably in the range of 5 to 30 dN·m. This is because, within this range, sufficient stress relaxation properties of the cured product can be realized and it is possible to achieve compatibility with the loss tangent (tan δ) described later. On the other hand, if the maximum torque value at the molding temperature of the cured product exceeds the above upper limit, the cured product will be excessively hard and will not achieve stress relaxation properties, which may result in warping or defects in the molded product, especially when integrally molded with a substrate.

[0020] Next, the condition of the loss tangent (tan δ) of the composition in the present invention will be explained. The loss tangent (tan δ) is a value measured by reading the value of the loss tangent (tan δ) expressed as the ratio of the storage torque value / loss torque value when the maximum torque value is reached by the measurement using the above-mentioned MDR. Here, the loss tangent (tan δ) of the composition being less than 0.2 means that the rubber elasticity of the cured product obtained by curing the composition is low and the surface is moderately hard, and the cured product is less likely to adhere / adsorb to the mold during demolding in the molding process, and has excellent demoldability. From the viewpoint of demoldability, the loss tangent (tan δ) of the cured product when the maximum torque value is reached is preferably in the range of 0.01 to 0.19, and particularly preferably in the range of 0.03 to 0.18. On the other hand, if the loss tangent (tan δ) of the composition exceeds 0.2, the rubber elasticity of the resulting cured product will be so high that its surface will become sticky, and the cured product will tend to adhere / adsorb to the mold during demolding, making it difficult to separate smoothly from the mold and resulting in insufficient demoldability.

[0021] By satisfying both the above-mentioned (1) maximum torque value condition and (2) loss tangent (tan δ) value condition, which is expressed as the ratio of stored torque value / loss torque value when the maximum torque value is reached, the curable silicone composition for transfer molding of the present invention achieves excellent stress relaxation properties in the cured product, is less prone to warping or defects, and achieves good demoldability.

[0022] [Composition of the curable silicone composition for transfer molding] The curable silicone composition for transfer molding of the present invention further comprises: (A) a curable reactive organopolysiloxane; (B) a functional filler, and (C) containing a curing agent, At least 50 mass % of the component (A) has a curing reactive functional group containing at least one carbon-carbon double bond in the (A1) molecule, and RSiO 3 / 2 (wherein R is a monovalent organic group) and a siloxane unit represented by SiO 4 / 2It is particularly preferable that the content of component (B) is 40% by volume or less of the entire composition. It is also preferable that the content of component (A1) is in the range of 20 to 80% by mass of the entire composition. Each component and optional component of the composition will be described below. In the present invention, the term "average particle size" refers to the average primary particle size of the particles unless otherwise defined.

[0023] [Component (A) mainly containing component (A1)] Component (A) is one of the main components of the composition and is one or more types of curable reactive organopolysiloxane having a curable reactive group in the molecule, and at least 50 mass % of the component (A) is (A1)RSiO 3 / 2 (wherein R is a monovalent organic group) and a siloxane unit represented by SiO 4 / 2 and having a curing reactive functional group containing a carbon-carbon double bond in the molecule. Component (A) may consist of only one or more types of component (A1), or it may be a mixture containing a curing reactive organopolysiloxane other than component (A1).

[0024] The composition preferably contains component (A1) in the range of 20 to 80% by mass, more preferably 30 to 75% by mass, of the entire composition. Such component (A1) is preferably waxy or solid at room temperature, and may be dissolved in component (A) other than component (A1) that is liquid at room temperature and used as a viscous liquid when producing a paste-like composition. When producing a hot-melt composition, it is preferably used in the form of fine particles, either alone or together with other components (e.g., part of component (C) which is a curing agent), and is particularly preferably spherical silicone fine particles with an average primary particle size of 1 to 20 μm.

[0025] The component (A1) must have a curing reactive group having a carbon-carbon double bond in the molecule. Such a curing reactive group is a functional group that is hydrosilylation reactive or organic peroxide curable, and forms a cured product by crosslinking with other components. Such a curing reactive group is an alkenyl group or an acrylic group, and examples of such a curing reactive group include alkenyl groups having 2 to 10 carbon atoms, such as vinyl groups, allyl groups, butenyl groups, pentenyl groups, hexenyl groups, and heptenyl groups; and acrylic group-containing monovalent organic groups, such as 3-methacryloxypropyl groups and 3-acryloxypropyl groups. In particular, a vinyl group or a hexenyl group is preferable.

[0026] Examples of groups bonded to silicon atoms other than the hydrosilylation reactive groups in component (A1) include alkyl groups having 1 to 20 carbon atoms, halogen-substituted alkyl groups having 1 to 20 carbon atoms, aryl groups having 6 to 20 carbon atoms, halogen-substituted aryl groups having 6 to 20 carbon atoms, aralkyl groups having 7 to 20 carbon atoms, alkoxy groups, and hydroxyl groups. Specific examples include alkyl groups such as methyl groups, ethyl groups, propyl groups, butyl groups, pentyl groups, hexyl groups, heptyl groups, octyl groups, nonyl groups, decyl groups, undecyl groups, and dodecyl groups; aryl groups such as phenyl groups, tolyl groups, xylyl groups, naphthyl groups, anthracenyl groups, phenanthryl groups, and pyrenyl groups; aralkyl groups such as phenethyl groups and phenylpropyl groups; and groups in which some or all of the hydrogen atoms bonded to these groups have been substituted with halogen atoms such as chlorine atoms and bromine atoms; and alkoxy groups such as methoxy groups, ethoxy groups, and propoxy groups. Phenyl groups and hydroxyl groups are particularly preferred. In particular, it is preferred that 10 mol % or more of all organic groups in the molecule of the component (A1) be aryl groups, and particularly phenyl groups.

[0027] The component (A1) is a major component that determines the curing behavior of the composition. The composition of the present invention has (1) a maximum torque value of less than 50 dN·m, measured by MDR (Moving Die Rheometer) at molding temperatures from room temperature to 200°C, and (2) a loss tangent (tan δ) value expressed as the ratio of storage torque value / loss torque value when the maximum torque value is reached is less than 0.2. In order to make the maximum torque value less than 50 dN·m, it is preferable that the glass transition temperature of the component (A1) is equal to or lower than the molding temperature. In addition, in order to make the tan δ value at the molding temperature less than 0.2, it is preferable that the glass transition temperature of the component (A1) is somewhat away from the molding temperature. However, if the glass transition point is significantly lower than room temperature, the strength of the obtained cured product at room temperature tends to be low. Therefore, it is preferable that the glass transition point of the component (A1) is substantially within the range of room temperature to the molding temperature, and more preferably within the range of room temperature to 100°C. From the viewpoint of improving the strength of the obtained cured product at room temperature, it is preferable that the glass transition temperature is room temperature or higher. In other words, it is preferable that component (A1) has hot melt properties, and specifically, it is preferable that component (A1) is non-flowable at 25°C and has a melt viscosity at 100°C of 8000 Pa s or less. Non-flowable means that it does not flow under no load, and indicates a state below the softening point measured by the ring and ball method for testing the softening point of hot melt adhesives specified in JIS K 6863-1994 "Testing method for the softening point of hot melt adhesives". In other words, to be non-flowable at 25°C, the softening point must be higher than 25°C.

[0028] The melt viscosity of component (A1) at 100°C is preferably 8000 Pa s or less, 5000 Pa s or less, or in the range of 10 to 3000 Pa s. When the melt viscosity at 100°C is within the above range, good adhesion is achieved after cooling to 25°C after hot melting.

[0029] When it is desired to impart hot melt properties to the composition of the present invention, it is preferable that the (A1) component and the entire (A) component including it are in the form of fine particles. The particle size is not limited, but the average primary particle size is preferably in the range of 1 to 5000 μm, 1 to 500 μm, 1 to 100 μm, 1 to 20 μm, or 1 to 10 μm. This average primary particle size can be determined, for example, by observing with an optical microscope or SEM. The shape of the (A1) component or the entire (A) component is not limited, and examples include spherical, spindle-shaped, plate-shaped, needle-shaped, and irregular shapes. Since it melts uniformly, it is preferable that it is spherical or true spherical. In particular, by making the entire (A) component true spherical with a diameter of 1 to 10 μm, the melting properties of the present blend and the mechanical properties after curing can be improved favorably.

[0030] The component (A1) is (A1) a resinous organopolysiloxane, (A2) an organopolysiloxane crosslinked product obtained by crosslinking at least one organopolysiloxane; (A3) a block copolymer consisting of a resinous organosiloxane block and a linear organosiloxane block; Or a mixture of at least two of these The silicone fine particles consisting of the above are preferred.

[0031] The (A1) component is a resinous organopolysiloxane having a hydrosilylation reactive group and / or a radical reactive group, and is preferably a hot-melt resinous organopolysiloxane having many T or Q units and an aryl group. Examples of such (A1) component include MQ resins, MDQ resins, MTQ resins, MDTQ resins, TD resins, TQ resins, and TDQ resins consisting of any combination of triorganosiloxy units (M units) (organo groups are methyl groups only, methyl groups and vinyl groups or phenyl groups), diorganosiloxy units (D units) (organo groups are methyl groups only, methyl groups and vinyl groups or phenyl groups), monoorganosiloxy units (T units) (organo groups are methyl groups, vinyl groups or phenyl groups), and siloxy units (Q units). The component (A1) has at least two hydrosilylation reactive groups and / or radical reactive groups in the molecule, and it is preferred that at least 10 mol % of all organic groups in the molecule are aryl groups, particularly phenyl groups.

[0032] In addition, since the component (A2) is formed by crosslinking at least one organopolysiloxane, cracks are unlikely to occur when cured with the curing agent (C), and curing shrinkage can be reduced. Here, "crosslinking" refers to linking the organopolysiloxane, which is the raw material, to the organopolysiloxane through a hydrosilylation reaction, a condensation reaction, a radical reaction, a high-energy ray reaction, or the like. Examples of the hydrosilylation reactive group and the radical reactive group (including a high-energy ray reactive group) include the same groups as those described above, and examples of the condensation reactive group include a hydroxyl group, an alkoxy group, and an acyloxy group.

[0033] The units constituting the (A2) component are not limited, and examples thereof include siloxane units and silalkylene group-containing siloxane units. In addition, since sufficient hardness and mechanical strength are imparted to the resulting cured product, it is preferable that the same molecule contains a resinous polysiloxane unit and a chain-like polysiloxane unit. In other words, the (A2) component is preferably a crosslinked product of a resinous (resinous) organopolysiloxane and a chain-like (including linear or branched) organopolysiloxane. By introducing a resinous organopolysiloxane structure-chain-like organopolysiloxane structure into the (A2) component, the (A2) component exhibits good hot melt properties and also exhibits good curability due to the (C) curing agent.

[0034] The component (A2) is (1) A resin-like organopolysiloxane structure and a linear organopolysiloxane structure are linked by alkylene bonds in a molecule via a hydrosilylation reaction between an organopolysiloxane having at least two alkenyl groups per molecule and an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule. (2) At least two organopolysiloxanes having at least two radical reactive groups in one molecule are subjected to a radical reaction with an organic peroxide, resulting in a resinous organopolysiloxane structure and a linear organopolysiloxane structure linked in the molecule by a siloxane bond or an alkylene bond. (3) A resin-like organopolysiloxane structure and a linear organopolysiloxane structure are linked in the molecule through a siloxane (-Si-O-Si-) bond via a condensation reaction of at least two types of organopolysiloxane. Such component (A2) has a structure in which the resin structure and the organopolysiloxane portion of the chain structure are linked by an alkylene group or a new siloxane bond, thereby significantly improving the hot melt properties.

[0035] In the above (1) and (2), examples of the alkylene group contained in component (A2) include alkenyl groups having 2 to 20 carbon atoms, such as ethylene group, propylene group, butylene group, pentylene group, and hexylene group, which may be linear or branched, and are preferably ethylene or hexylene groups.

[0036] The crosslinked product of the resinous organopolysiloxane and the chain (including linear and branched) organopolysiloxane is composed, for example, of the following siloxane units and silalkylene group-containing siloxane units. M unit:R 1 R 2 2SiO 1 / 2 A siloxane unit represented by the formula: D unit:R 1 R 2 SiO 2 / 2 A siloxane unit represented by the formula: R 3 M / R 3 D unit:R 3 1 / 2 R 2 2SiO 1 / 2 and R 3 1 / 2 R 2 SiO 2 / 2 At least one siloxane unit selected from silalkylene group-containing siloxane units represented by the formula: T / Q unit:R 2 SiO 3 / 2 and SiO 4 / 2 At least one siloxane unit selected from the siloxane units represented by

[0037] In the formula, R 1 are each independently an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and examples of these groups are the same as those mentioned above. 1is preferably a methyl group, a vinyl group, or a phenyl group. However, among all the siloxane units, at least two R 1 is preferably an alkenyl group.

[0038] In addition, in the formula, R 2 each independently represents an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms; 1 Examples of the groups are the same as those shown in R 2 is preferably a methyl group or a phenyl group.

[0039] In addition, in the formula, R 3 is a linear or branched alkylene group having 2 to 20 carbon atoms bonded to a silicon atom in another siloxane unit. Examples of the alkylene group include the same groups as those mentioned above, and an ethylene group or a hexylene group is preferred.

[0040] The M unit is a siloxane unit constituting the terminal of the component (A2), and the D unit is a siloxane unit constituting a linear polysiloxane structure. It is preferable that an alkenyl group is present on the M unit or D unit, particularly on the M unit. 3 M units and R 3 The D unit is a siloxane unit that is bonded to a silicon atom in another siloxane unit via a silalkylene bond and to a silicon atom in another siloxane unit via an oxygen atom. The T / Q unit is a branched siloxane unit that gives the polysiloxane a resinous structure. The (A2) component is R 2 SiO 3 / 2 and / or SiO 4 / 2 In particular, in order to improve the hot melt properties of the component (A2) and adjust the content of aryl groups in the component (A2), it is preferable that the component (A2) contains a siloxane unit represented by R 2 SiO 3 / 2 It is preferable that the siloxane unit represented by R 2 It is preferred that the siloxane unit contains a phenyl group.

[0041] R 3 M / R 3 The D unit is one of the characteristic structures of the (A2) component, and R 3 It represents a structure in which silicon atoms are bridged via an alkylene group of the formula: 3 1 / 2 R 2 2SiO 1 / 2 and an alkylene group-containing siloxane unit represented by R 3 1 / 2 R 2 SiO 2 / 2 Of all the siloxane units constituting component (A2), at least two are preferably alkylene group-containing siloxane units represented by the formula: 3 The preferred bond between the siloxane units having an alkylene group is as described above, and the bond between the two alkylene group-containing siloxane units is R 3 The number of is expressed as a bond valence of "1 / 2" like oxygen in the M unit. If R 3 If the number of is 1, then [O 1 / 2 R 2 2SiR 3 SiR 2 2O 1 / 2 ], [O 1 / 2 R 2 2SiR 3 SiR 2 O 2 / 2 ] and [O 2 / 2 R 2 SiR 3 SiR 2 O 2 / 2 In component (A2), at least one selected from the structural units of siloxanes represented by the formula:] is contained, and each oxygen atom (O) is bonded to a silicon atom contained in the aforementioned M, D, or T / Q unit. By having such a structure, component (A2) can be relatively easily designed to have a structure in which a linear polysiloxane structure consisting of D units and a resinous polysiloxane structure containing T / Q units are contained within the molecule, and the physical properties of the component (A2) are remarkably excellent.

[0042] In the above (1), the compound can be obtained by subjecting an organopolysiloxane having at least two alkenyl groups per molecule and an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule to a hydrosilylation reaction in a reaction ratio such that [number of moles of alkenyl groups] / [number of moles of silicon-bonded hydrogen atoms]>1.

[0043] In the above (2), at least two types of organopolysiloxanes each having at least two radical reactive groups in one molecule can be obtained by radical reaction with an organic peroxide in an amount that is insufficient to react with all of the radical reactive groups in the system.

[0044] In the above (1) and (2), component (A2) is a product of a hydrosilylation reaction or radical reaction between an organopolysiloxane having a resinous siloxane structure and an organopolysiloxane having a chain siloxane structure.

[0045] For example, the component (A2) is (A R ) R in the molecule 2 SiO 3 / 2 (In the formula, R 2 is the same group as above.) and / or SiO 4 / 2 and having an alkenyl group having 2 to 20 carbon atoms, a silicon-bonded hydrogen atom, or a radical-reactive group; and (A L ) R in the molecule 2 2SiO 2 / 2 A siloxane unit represented by the formula: 2 is the same group as above. R ) at least one linear organopolysiloxane having a group capable of hydrosilylation or radical reaction with component (a), the group being an alkenyl group having 2 to 20 carbon atoms or a silicon-bonded hydrogen atom, (A R ) component or (A L) is an organopolysiloxane obtained by reacting the two components in a ratio designed so that the hydrosilylation reactive groups and / or radical reactive groups in the two components remain after the reaction.

[0046] In the above (1), (A R When at least a portion of the component (A) is a resinous organopolysiloxane having an alkenyl group having 2 to 20 carbon atoms, L It is preferable that at least a portion of the component (a) is a linear organopolysiloxane having silicon-bonded hydrogen atoms.

[0047] Similarly, (A R When at least a portion of component (A) is a resinous organopolysiloxane having silicon-bonded hydrogen atoms, L At least a portion of the ) component is preferably a chain organopolysiloxane having an alkenyl group having 2 to 20 carbon atoms.

[0048] Such an (A2) component is (a1) Component: 1-1 ) ingredients and / or the following (a 1-2 ) an organopolysiloxane having at least two alkenyl groups having 2 to 20 carbon atoms in the molecule, which is subjected to a radical reaction with an organic peroxide; or Component (a1), (a2) an organohydrogenpolysiloxane, It is preferable that the hydrosilylation reaction is carried out in the presence of a hydrosilylation catalyst such that the molar ratio of silicon-bonded hydrogen atoms in component (a2) is 0.2 to 0.7 mol per mol of alkenyl groups having 2 to 20 carbon atoms in component (a1).

[0049] (a 1-1 ) component is a polysiloxane having a relatively high amount of branched units and has the average unit formula: (R 4 3SiO 1 / 2 ) a (R 4 2SiO 2 / 2 ) b (R4 SiO 3 / 2 ) c (SiO 4 / 2 ) d (R 5 O 1 / 2 ) e In the formula, R 4 each independently represents an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms; 1 Examples of the groups are the same as those shown in R 4 is preferably a methyl group, a vinyl group, or a phenyl group, provided that R 4 At least two of R are alkenyl groups. In addition, since the hot melt property is good, 4 Preferably, 10 mol % or more, or 20 mol % or more of R 5 is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and examples of the alkyl group include the same as those mentioned above.

[0050] In the formula, a is a number within the range of 0 to 0.7, b is a number within the range of 0 to 0.7, c is a number within the range of 0 to 0.9, d is a number within the range of 0 to 0.7, e is a number within the range of 0 to 0.1, and c+d is a number within the range of 0.3 to 0.9, and a+b+c+d is 1, and preferably a is a number within the range of 0 to 0.6, b is a number within the range of 0 to 0.6, c is a number within the range of 0 to 0.9, d is a number within the range of 0 to 0.5, e is a number within the range of 0 to 0.05, and c+d is a number within the range of 0.4 to 0.9, and a+b+c+d is 1. This is because when a, b, and c+d are each a number within the above range, the hardness and mechanical strength of the obtained cured product are excellent.

[0051] Such (a 1-1 ) component includes the following organopolysiloxanes: In the formula, Me, Ph, and Vi represent a methyl group, a phenyl group, and a vinyl group, respectively. (ViMe2SiO 1 / 2 , 0.25 (PhSiO 3 / 2 , 0.75 (HO 1 / 2 , 0.02 (ViMe2SiO 1 / 2 , 0.25 (PhSiO 3 / 2 , 0.75 (ViMe2SiO 1 / 2 , 0.20 (PhSiO 3 / 2 , 0.80 (ViMe2SiO 1 / 2 , 0.15 (Me3SiO 1 / 2 , 0.38 (SiO 4 / 2 , 0.47 (H 1 / 2 , 0.01 (ViMe2SiO 1 / 2 , 0.13 (Me3SiO 1 / 2 , 0.45 (SiO 4 / 2 , 0.42 (H 1 / 2 , 0.01 (ViMe2SiO 1 / 2 , 0.15 (PhSiO 3 / 2 , 0.85 (H 1 / 2 , 0.01 (Me2SiO 2 / 2 , 0.15 (MeViSiO 2 / 2 , 0.10 (PhSiO 3 / 2 , 0.75 (H 1 / 2 , 0.04 (MeViPhSiO 1 / 2 , 0.20 (PhSiO 3 / 2 , 0.80 (H 1 / 2 , 0.05 (ViMe2SiO 1 / 2 , 0.15 (PhSiO 3 / 2 , 0.75(SiO 4 / 2 ) 0.10 (HO 1 / 2 ) 0.02 (Ph2SiO 2 / 2 ) 0.25 (MeViSiO 2 / 2 ) 0.30 (PhSiO 3 / 2 ) 0.45 (HO 1 / 2 ) 0.04 (Me3SiO 1 / 2 ) 0.20 (ViMePhSiO 1 / 2 ) 0.40 (SiO 4 / 2 ) 0.40 (HO 1 / 2 ) 0.08

[0052] (a 1-2 ) component is a polysiloxane having a relatively large amount of linear siloxane units and has the average unit formula: (R 4 3SiO 1 / 2 ) a' (R 4 2SiO 2 / 2 ) b' (R 4 SiO 3 / 2 ) c' (SiO 4 / 2 ) d' (R 5 O 1 / 2 ) e' In the formula, R is an organopolysiloxane having at least two alkenyl groups having 2 to 20 carbon atoms in one molecule. 4 and R 5 is the same group as defined above.

[0053] In the formula, a' is a number within the range of 0.01 to 0.3, b' is a number within the range of 0.4 to 0.99, c' is a number within the range of 0 to 0.2, d' is a number within the range of 0 to 0.2, e' is a number within the range of 0 to 0.1, and c'+d' is a number within the range of 0 to 0.2, and a'+b'+c'+d' is 1, and preferably a' is a number within the range of 0.02 to 0.20, b' is a number within the range of 0.6 to 0.99, c' is a number within the range of 0 to 0.1, d' is a number within the range of 0 to 0.1, j' is a number within the range of 0 to 0.05, and c'+d' is a number within the range of 0 to 0.1, and a'+b'+c'+d' is 1. This is because when a', b', c', and d' are each numbers within the above ranges, toughness can be imparted to the obtained cured product.

[0054] Such (a 1-2 ) component includes the following organopolysiloxanes: In the formula, Me, Ph, and Vi represent a methyl group, a phenyl group, and a vinyl group, respectively. ViMe2SiO(MePhSiO) 18 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.10 (MePhSiO 2 / 2 ) 0.90 ViMe2SiO(MePhSiO) 30 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.063 (MePhSiO 2 / 2 ) 0.937 ViMe2SiO(MePhSiO) 150 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.013 (MePhSiO 2 / 2 ) 0.987 ViMe2SiO(Me2SiO) 18 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.10 (MeSiO 2 / 2 ) 0.90 ViMe2SiO(Me2SiO) 30 SiMe2Vi, i.e. (ViMe2SiO1 / 2 ) 0.063 (MeSiO 2 / 2 ) 0.937 ViMe2SiO(Me2SiO) 35 (MePhSiO) 13 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.04 (MeSiO 2 / 2 ) 0.70 (MePhSiO 2 / 2 ) 0.26 ViMe2SiO(Me2SiO) 10 SiMe2Vi, i.e. (ViMe2SiO 1 / 2 ) 0.17 (MeSiO 2 / 2 ) 0.83 (ViMe2SiO 1 / 2 ) 0.10 (MePhSiO 2 / 2 ) 0.80 (PhSiO 3 / 2 ) 0.10 (HO 1 / 2 ) 0.02 (ViMe2SiO 1 / 2 ) 0.20 (MePhSiO 2 / 2 ) 0.70 (SiO 4 / 2 ) 0.10 (HO 1 / 2 ) 0.01 HOMe2SiO(MeViSiO) 20 SiMe2OH Me2ViSiO(MePhSiO) 30 SiMe2Vi Me2ViSiO(Me2SiO) 150 SiMe2Vi

[0055] (a 1-1 The component (a) is preferably used from the viewpoint of imparting hardness and mechanical strength to the resulting cured product. 1-2Component (a2) can be added as an optional component from the viewpoint of imparting toughness to the obtained cured product, but when a crosslinking agent having many linear siloxane units is used in component (a2) below, it may be substituted therewith. In either case, the mass ratio of the component having many branched siloxane units to the component having many linear siloxane units is preferably within the range of 50:50 to 100:0, or within the range of 60:40 to 100:0. This is because when the mass ratio of the component having many branched siloxane units to the component having many linear siloxane units is within the above range, the hardness and mechanical strength of the obtained cured product are good.

[0056] In addition, when the component (a1) is subjected to a radical reaction with an organic peroxide, 1-1 ) component and (a 1-2 ) components in a ratio of 10:90 to 90:10, and it is possible to eliminate the need to use component (a2).

[0057] The component (a2) is a compound represented by the formula (a 1-1 ) component and / or (a 1-2 (a2) is a component for crosslinking component (a1) and is an organopolysiloxane containing at least two silicon-bonded hydrogen atoms in one molecule. Examples of groups bonded to silicon atoms other than hydrogen atoms in component (a2) include alkyl groups having 1 to 20 carbon atoms, halogen-substituted alkyl groups having 1 to 20 carbon atoms, aryl groups having 6 to 20 carbon atoms, halogen-substituted aryl groups having 6 to 20 carbon atoms, aralkyl groups having 7 to 20 carbon atoms, alkoxy groups, epoxy-containing groups, and hydroxyl groups, and examples of such groups are the same as those mentioned above.

[0058] Although there are no limitations on such component (a2), it is preferable that the component (a2) has the average composition formula: R 6 k H m SiO (4-k-m) / 2 In the formula, R 6is an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, 1 Of these, a methyl group or a phenyl group is preferable.

[0059] In the formula, k is a number in the range of 1.0 to 2.5, and preferably a number in the range of 1.2 to 2.3, m is a number in the range of 0.01 to 0.9, and preferably a number in the range of 0.05 to 0.8, and k+m is a number in the range of 1.5 to 3.0, and preferably a number in the range of 2.0 to 2.7.

[0060] The component (a2) may be a resinous organohydrogenpolysiloxane having a large number of branched siloxane units, or a linear organohydrogenpolysiloxane having a large number of linear siloxane units. 2-1 ), an organohydrogenpolysiloxane represented by the following (a 2-2 ) or a mixture thereof.

[0061] (a 2-1 ) ingredients are average unit formula: [R 7 3SiO 1 / 2 ] f [R 7 2SiO 2 / 2 ] g [R 7 SiO 3 / 2 ] h [SiO 4 / 2 ] i (R 5 O 1 / 2 ) j In the formula, R 7each independently represents an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, or a hydrogen atom, 1 In addition, in the formula, R 5 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and examples thereof include the same groups as those mentioned above.

[0062] In the formula, f is a number in the range of 0 to 0.7, g is a number in the range of 0 to 0.7, h is a number in the range of 0 to 0.9, i is a number in the range of 0 to 0.7, j is a number in the range of 0 to 0.1, and h+i is a number in the range of 0.3 to 0.9, and f+g+h+i is 1, and preferably, f is a number in the range of 0 to 0.6, g is a number in the range of 0 to 0.6, h is a number in the range of 0 to 0.9, i is a number in the range of 0 to 0.5, j is a number in the range of 0 to 0.05, and h+i is a number in the range of 0.4 to 0.9, and f+g+h+i is 1.

[0063] (a 2-2 ) ingredients are average unit formula: (R 7 3SiO 1 / 2 ) f' (R 7 2SiO 2 / 2 ) g' (R 7 SiO 3 / 2 ) h' (SiO 4 / 2 ) i' (R 5 O 1 / 2 ) j' In the formula, R is an organopolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule. 7 and R 5 is the same group as defined above.

[0064] Furthermore, in the formula, f' is a number in the range of 0.01 to 0.3, g' is a number in the range of 0.4 to 0.99, h' is a number in the range of 0 to 0.2, i' is a number in the range of 0 to 0.2, j' is a number in the range of 0 to 0.1, and h'+i' is a number in the range of 0 to 0.2, and f'+g'+h'+i' is 1, and preferably f' is a number in the range of 0.02 to 0.20, g' is a number in the range of 0.6 to 0.99, h' is a number in the range of 0 to 0.1, i' is a number in the range of 0 to 0.1, j' is a number in the range of 0 to 0.05, and h'+i' is a number in the range of 0 to 0.1, and f'+g'+h'+i' is 1.

[0065] As described above, in the component (a2), the resin-like organopolysiloxane having a large number of branched siloxane units imparts hardness and mechanical strength to the cured product, while the resulting organopolysiloxane having a large number of linear siloxane units imparts toughness to the cured product. 2-1 ) component and (a 2-2 Specifically, when the branched siloxane unit is small in the (a1) component, it is preferable to use (a 2-1 It is preferable to mainly use component (a1), and when the amount of linear siloxane units in component (a1) is small, it is preferable to mainly use component (a 2-2 It is preferable to mainly use the component (a2). 2-1 ) component and (a 2-2 ) The mass ratio of the components is preferably within the range of 50:50 to 100:0, or 60:40 to 100:0.

[0066] An example of such component (a2) is the following organopolysiloxane: In the formula, Me and Ph represent a methyl group and a phenyl group, respectively. Ph2Si(OSiMe2H)2, i.e., Ph 0.67 Me 1.33 H 0.67 SiO 0.67 HMe2SiO(Me2SiO) 20 SiMe2H, i.e., Me 2.00 H 0.09 SiO 0.95 HMe2SiO(Me2SiO) 55 SiMe2H, i.e., Me 2.00 H 0.04 SiO 0.98 PhSi(OSiMe2H)3, i.e., Ph 0.25 Me 1.50 H 0.75 SiO 0.75 (HMeSiO 1 / 2 ) 0.6 (PhSiO 3 / 2 ) 0.4 , i.e., Ph 0.40 Me 1.20 H 0.60 SiO 0.90

[0067] The amount of component (a2) added is an amount such that the molar ratio of silicon-bonded hydrogen atoms in component (a2) to the alkenyl groups in component (a1) is 0.2 to 0.7, and preferably 0.3 to 0.6, because when the amount of component (a2) added is within the above range, the initial hardness and mechanical strength of the resulting cured product are good.

[0068] The organic peroxide used for the radical reaction of the component (a1) is not limited, and the organic peroxides exemplified in the component (C) below can be used. 1-1 ) component and (a 1-2 It is preferable that the mass ratio of the (a1) components is within the range of 10:90 to 90:10. The amount of the organic peroxide added is not limited, but is preferably within the range of 0.1 to 5 parts by mass, 0.2 to 3 parts by mass, or 0.2 to 1.5 parts by mass, per 100 parts by mass of the (a1) component.

[0069] The hydrosilylation catalyst used to subject the components (a1) and (a2) to the hydrosilylation reaction is not limited, and any of the hydrosilylation catalysts exemplified for component (C) below can be used. The amount of the hydrosilylation catalyst added is preferably such that the platinum-based metal atom in the hydrosilylation catalyst is, by mass unit, within the range of 0.01 to 500 ppm, 0.01 to 100 ppm, or 0.01 to 50 ppm relative to the total amount of components (a1) and (a2).

[0070] The above component (A3) is obtained by subjecting the following components (a3) ​​and (a4) to a condensation reaction in the presence of a condensation reaction catalyst.

[0071] (a3) Component has the average unit formula: (R 8 3SiO 1 / 2 ) p (R 8 2SiO 2 / 2 ) q (R 8 SiO 3 / 2 ) r (SiO 4 / 2 ) s (R 9 O 1 / 2 ) t In the formula, R 8 are each independently an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and examples of these groups are the same as those mentioned above. 9 is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an acyl group having 2 to 5 carbon atoms, and examples of such groups include alkoxy groups such as methoxy and ethoxy groups, and acyloxy groups. Component (a3) ​​has at least one silicon-bonded hydroxyl group, silicon-bonded alkoxy group, or silicon-bonded acyloxy group in each molecule. In addition, at least two R 8 is an alkenyl group, and all R 8It is preferable that 10 mol % or more, or 20 mol % or more of these groups are phenyl groups.

[0072] In the formula, p is a number within the range of 0 to 0.7, q is a number within the range of 0 to 0.7, r is a number within the range of 0 to 0.9, s is a number within the range of 0 to 0.7, t is a number within the range of 0.01 to 0.10, and r+s is a number within the range of 0.3 to 0.9, and p+q+r+s is 1, and preferably, p is a number within the range of 0 to 0.6, q is a number within the range of 0 to 0.6, r is a number within the range of 0 to 0.9, s is a number within the range of 0 to 0.5, t is a number within the range of 0.01 to 0.05, and r+s is a number within the range of 0.4 to 0.9. This is because, when p, q, and r+s are each a number within the above range, a hot-melt silicone can be obtained that has flexibility at 25°C, is non-fluid, has low surface tack, and has a sufficiently low melt viscosity at high temperatures.

[0073] (a4) Component has the average unit formula: (R 8 3SiO 1 / 2 ) p' (R 8 2SiO 2 / 2 ) q' (R 8 SiO 3 / 2 ) r' (SiO 4 / 2 ) s' (R 9 O 1 / 2 ) t' In the formula, R 8 and R 9is the same group as above. Component (a4) has at least one silicon-bonded hydroxyl group, silicon-bonded alkoxy group, or silicon-bonded acyloxy group in one molecule. In the formula, p' is a number in the range of 0.01 to 0.3, q' is a number in the range of 0.4 to 0.99, r' is a number in the range of 0 to 0.2, s' is a number in the range of 0 to 0.2, t' is a number in the range of 0 to 0.1, and r'+s' is a number in the range of 0 to 0.2, and p'+q'+r'+s' is 1, and preferably p' is a number in the range of 0.02 to 0.20, q' is a number in the range of 0.6 to 0.99, r' is a number in the range of 0 to 0.1, s' is a number in the range of 0 to 0.1, t' is a number in the range of 0 to 0.05, and r'+s' is a number in the range of 0 to 0.1. This is because, when p', q', r', and s' are each numbers within the above ranges, a hot-melt silicone can be obtained that has flexibility at 25°C, yet is non-flowable, has low surface tack, and has a sufficiently low melt viscosity at high temperatures.

[0074] The condensation reaction catalyst for the condensation reaction of the components (a3) ​​and (a4) is not limited, and examples thereof include organotin compounds such as dibutyltin dilaurate, dibutyltin diacetate, tin octenate, dibutyltin dioctate, and tin laurate; organotitanium compounds such as tetrabutyl titanate, tetrapropyl titanate, and dibutoxybis(ethylacetoacetate); acidic compounds such as hydrochloric acid, sulfuric acid, and dodecylbenzenesulfonic acid; alkaline compounds such as ammonia and sodium hydroxide; and amine compounds such as 1,8-diazabicyclo[5.4.0]undecene (DBU) and 1,4-diazabicyclo[2.2.2]octane (DABCO). Of these, organotin compounds and organotitanium compounds are preferred.

[0075] The component (A3) is a block copolymer consisting of a resinous organosiloxane block and a linear organosiloxane block. The component (A3) preferably contains 40 to 90 mol % of a compound represented by the formula [R 1 2SiO 2 / 2 10 to 60 mol % of disiloxy units of the formula [R 1 SiO 3 / 2It is preferable that the trisiloxy unit is composed of the above-mentioned trisiloxy unit [≡SiOH] and contains 0.5 to 35 mol % of silanol groups [≡SiOH]. 1 are each independently an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and examples of which are the same as those mentioned above. 1 is an alkenyl group. 1 2SiO 2 / 2 ] forms linear blocks having an average of 100 to 300 disiloxy units per linear block, and the trisiloxy units [R 1 SiO 3 / 2 ] is a resinous organosiloxane block copolymer having a weight average molecular weight of at least 20,000 g / mole and containing 0.5-4.5 mol % of at least one alkenyl group, wherein at least 30% of the non-linear blocks are bonded to each other and each linear block is bonded to at least one non-linear block via a -Si-O-Si- bond, and wherein the resinous organosiloxane block copolymer has a weight average molecular weight of at least 20,000 g / mole and contains 0.5-4.5 mol % of at least one alkenyl group.

[0076] The component (A3) is prepared by a condensation reaction of (a5) a resinous organosiloxane or a resinous organosiloxane block copolymer, (a6) a linear organosiloxane, and, if necessary, (a7) a siloxane compound.

[0077] (a5) The component has the average unit formula: [R 1 2R 2 SiO 1 / 2 ] i [R 1 R 2 SiO 2 / 2 ] ii [R 1 SiO 3 / 2 ] iii [R 2 SiO 3 / 2 ] iv [SiO 4 / 2 ] v In the formula, R 1 are each independently an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms, and examples of the same groups as those mentioned above are given. 2 each independently represents an alkyl group having 1 to 20 carbon atoms, a halogen-substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a halogen-substituted aryl group having 6 to 20 carbon atoms, or an aralkyl group having 7 to 20 carbon atoms; 1 Examples of the groups are the same as those shown below.

[0078] In the formula, i, ii, iii, iv, and v represent the mole fraction of each siloxy unit, where i is a number from 0 to 0.6, ii is a number from 0 to 0.6, iii is a number from 0 to 1, iv is a number from 0 to 1, and v is a number from 0 to 0.6, with the proviso that ii+iii+iv+v>0 and i+ii+iii+iv+v≦1. In addition, the component (a5) preferably contains 0 to 35 mol % of silanol groups [≡SiOH] in one molecule.

[0079] The component (a6) has the general formula: R 1 3-α (X) α SiO(R 1 2SiO) β Si(X) α R 1 3-α In the formula, R 1 is the same as above, and examples thereof include the same groups as above. 5 , F, Cl, Br, I, -OC(O)R 5 , -N(R 5 )2, or -ON=CR 5 2 (where R 5is a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.) In the formula, each α is independently 1, 2, or 3, and β is an integer of 50 to 300.

[0080] The component (a7) has the general formula: R 1 R 2 2SiX In the formula, R 1 , R 2 and X are the same groups as defined above.

[0081] The condensation reaction catalyst for the condensation reaction of component (a5) with component (a6) and / or component (a7) is not limited, and examples thereof include organic tin compounds such as dibutyltin dilaurate, dibutyltin diacetate, tin octenate, dibutyltin dioctate, and tin laurate; organic titanium compounds such as tetrabutyl titanate, tetrapropyl titanate, and dibutoxybis(ethylacetoacetate); acidic compounds such as hydrochloric acid, sulfuric acid, and dodecylbenzenesulfonic acid; alkaline compounds such as ammonia and sodium hydroxide; and amine compounds such as 1,8-diazabicyclo[5.4.0]undecene (DBU) and 1,4-diazabicyclo[2.2.2]octane (DABCO).

[0082] In the present invention, a particularly preferred component (A1) is (A3) a block copolymer consisting of a resinous organosiloxane block and a linear organosiloxane block, in which RSiO 3 / 2 (wherein R is a monovalent organic group) and a siloxane unit represented by SiO 4 / 2 The siloxane units selected from the siloxane units represented by the formula (I) are in the range of 25 to 75 mol % of the total siloxane units, and R A SiO 3 / 2 (In the formula, R A is an aryl group having 6 to 20 carbon atoms).

[0083] Particularly preferably, component (A1) is in the form of fine organopolysiloxane particles having hot melt properties, in which 10 mol % or more, preferably 15 to 50 mol %, of all organic groups in the molecule are aryl groups, particularly phenyl groups. Meanwhile, in the present invention, component (A1) can be used without restrictions as long as it satisfies the above structure, but since the structure of component (A1) greatly affects the curing behavior of the entire composition, it is preferable that the melting point of the entire component (A1) is 200°C or less. Meanwhile, R'3SiO 1 / 2 (M unit, R' is an organic group other than an aryl group) and SiO 4 / 2 Since so-called MQ resins consisting of siloxane units (Q units) represented by the formula generally have a melting point exceeding 200° C., it is preferable to design the melting point of the mixture (A1) to be 200° C. or lower, preferably in the range of 25° C. to 200° C., by mixing in an appropriate ratio with another (A1) component having a melting point below 200° C. and a high content of aryl groups, particularly phenyl groups, among all organic groups in the molecule. If the content of the high-melting-point MQ resin component increases, the loss tangent (tan δ) of the curing behavior of the composition of the present invention tends to be high when measured by MDR, and this may make the composition unsuitable as a means for solving the problems of the present invention.

[0084] When it is desired to impart hot melt properties to the composition of the present invention, the component (A1) is preferably a particulate organopolysiloxane resin, and is preferably a spherical organopolysiloxane resin particulate having an average primary particle diameter of 1 to 20 μm as measured by a laser diffraction / scattering method or the like. By using such a particulate component, the present composition can be prepared or produced as a hot melt curable composition with excellent handling and hot melt properties. The production method can be a method of simply particulating the component (A), or a method of simultaneously or separately carrying out a step of crosslinking at least two types of organopolysiloxanes and a step of particulating the reaction product.

[0085] Examples of methods for producing the finely divided (A1) component include a method of pulverizing the above-mentioned organopolysiloxane resin using a pulverizer, and a method of directly pulverizing the resin in the presence of a solvent. The pulverizer is not limited, and examples thereof include a roll mill, a ball mill, a jet mill, a turbo mill, and a planetary mill. Examples of methods for directly pulverizing the organopolysiloxane resin in the presence of a solvent include spraying using a spray dryer, or pulverization using a two-screw kneader or a belt dryer. When obtaining a finely divided polyorganosiloxane, the (A1) component having a different structure, other organopolysiloxane components, and a curing catalyst described below, such as a hydrosilylation reaction catalyst, may be pulverized together, but from the viewpoint of the storage stability of the obtained composition, it is better to avoid pulverizing a mixture that can be cured by heat. Specifically, it is preferable to pulverize a part of the (A1) component, other (A) components, and (C) component, and add the remaining components when obtaining the composition by the method described below. In the present invention, the use of spherical hot-melt silicone microparticles obtained by spraying with a spray dryer is particularly preferred from the standpoints of the melting characteristics of the granular compound, the flexibility of the cured product, the amount of component (B) used, production efficiency, and the handling and workability of the composition.

[0086] By using a spray dryer or the like, it is possible to produce component (A) or component (A1) that is spherical and has an average primary particle diameter of 1 to 500 μm. The heating and drying temperature of the spray dryer must be appropriately set based on the heat resistance of the silicone microparticles. In order to prevent secondary aggregation of the silicone microparticles, it is preferable to control the temperature of the silicone microparticles to be below their glass transition temperature. The silicone microparticles thus obtained can be collected using a cyclone, bag filter, or the like.

[0087] In order to obtain a uniform (A) component or (A1) component, a solvent may be used in the above steps within the range that does not inhibit the curing reaction. The solvent is not limited, but examples thereof include aliphatic hydrocarbons such as n-hexane, cyclohexane, and n-heptane; aromatic hydrocarbons such as toluene, xylene, and mesitylene; ethers such as tetrahydrofuran and dipropyl ether; silicones such as hexamethyldisiloxane, octamethyltrisiloxane, and decamethyltetrasiloxane; esters such as ethyl acetate, butyl acetate, and propylene glycol monomethyl ether acetate; and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0088] The component (A) may contain a curable reactive organopolysiloxane other than the component (A1). For example, RSiO 3 / 2 (wherein R is a monovalent organic group) and a siloxane unit represented by SiO 4 / 2 Examples of the organopolysiloxane include linear or branched organopolysiloxanes having a content of siloxane units represented by the formula (I) of less than 20 mol % and having at least one, preferably two or more, curing reactive functional groups in the molecule containing a carbon-carbon double bond. The types of curing reactive functional groups can be the same as those described above, but are preferably hydrosilylation reactive or organic peroxide curing functional groups, particularly vinyl or hexenyl groups. The binding site of the curing reactive functional group may be the molecular chain terminal or a side chain (pendant site) of the siloxane molecular chain. The functional groups other than the curing reactive functional groups containing a carbon-carbon double bond are not particularly limited, and may be alkyl groups, aryl groups, hydroxyl groups, or alkoxy groups that may be substituted with halogen atoms.

[0089] [(B) Component] The functional filler, which is the component (B) of the present invention, is a component that imparts mechanical properties and other properties to the cured product. When cured at high temperatures after heat melting (hot melt), the cured product has the desired functions, and depending on the selection and amount of the component (B), a cured product excellent in hardness and toughness can be obtained from room temperature to high temperatures. Examples of the component (B) include inorganic fillers, organic fillers, and mixtures thereof. Examples of the inorganic fillers include reinforcing fillers, white pigments, thermally conductive fillers, conductive fillers, phosphors, and mixtures of at least two of these, and examples of the organic fillers include silicone resin-based fillers, fluororesin-based fillers, and polybutadiene resin-based fillers. The shape of these fillers is not particularly limited, and may be spherical, spindle-shaped, flat, needle-shaped, amorphous, etc.

[0090] When the present composition is used as a sealant, protective agent, adhesive, light reflector, or the like, it is preferable for at least a part of component (B) to contain a reinforcing filler, from the viewpoint of improving the mechanical strength, protective properties, and adhesive properties of the cured product.

[0091] The reinforcing filler can be added to improve the mechanical strength of the cured product, improve protection and adhesion, and also to maintain the solid particulate state as a binder filler of the curable granular silicone composition before curing. Examples of such reinforcing fillers include fumed silica, precipitated silica, fused silica, calcined silica, fumed titanium dioxide, quartz, calcium carbonate, diatomaceous earth, aluminum oxide, aluminum hydroxide, zinc oxide, and zinc carbonate. In addition, these reinforcing fillers can be surface-treated with organoalkoxysilanes such as methyltrimethoxysilane; organohalosilanes such as trimethylchlorosilane; organosilazanes such as hexamethyldisilazane; siloxane oligomers such as α,ω-silanol group-blocked dimethylsiloxane oligomers, α,ω-silanol group-blocked methylphenylsiloxane oligomers, and α,ω-silanol group-blocked methylvinylsiloxane oligomers. The particle size of the reinforcing filler is not limited, but the median size measured by laser diffraction / scattering particle size distribution measurement is preferably within the range of 1 nm to 500 μm.Furthermore, fibrous fillers such as calcium metasilicate, potassium titanate, magnesium sulfate, sepiolite, zonolite, aluminum borate, rock wool, and glass fiber may be used as the reinforcing filler.

[0092] Here, it is preferable that the (B) component is an inorganic filler that does not substantially contain coarse particles with an average particle size of 10.0 μm or more, and in particular, when the curable silicone composition for transfer molding of the present invention is hot melt, it is possible to provide a curable silicone composition that has excellent gap filling properties when melted and cures to give a soft cured product at room temperature to high temperatures. Here, "substantially not containing coarse particles with an average particle size of 10.0 μm or more or 5.0 μm or more" means that when the (B) component is observed with an electron microscope or the like, no coarse particles with an average particle size of 10.0 μm or more or 5.0 μm or more are observed in the major axis of the particles, or when the particle size distribution of the (B) component is measured by a laser diffraction scattering type particle size distribution measurement or the like, the volume ratio of coarse particles with an average particle size of 10.0 μm or more or 5.0 μm or more is less than 1%.

[0093] Furthermore, when the curable silicone composition for transfer molding of the present invention is a hot melt composition, from the standpoint of imparting good gap-filling properties when molten and imparting flexibility of the cured product at room temperature to high temperatures, it is preferable that component (B) is a mixture of (b1) an inorganic filler having an average particle size of 0.1 μm or less, preferably a reinforcing filler, and (b2) an inorganic filler having an average particle size of 0.1 to 5.0 μm, preferably a reinforcing filler. The blending ratio of the two is arbitrary, but may be a mass ratio of 1 / 99 to 20 / 80, 1 / 99 to 50 / 50, or 5 / 95 to 40 / 60. In particular, (b1-1) fumed silica having an average particle size of 0.1 μm or less, preferably 0.05 μm or less, and (b2-1) fused silica having an average particle size of 0.1 to 5.0 μm, preferably 0.15 to 4.0 μm, may be contained in a ratio of 1 / 99 to 20 / 80, preferably 1 / 99 to 50 / 50, more preferably 5 / 95 to 40 / 60 by mass. In particular, when the particles of the mixture of inorganic fillers are the same or smaller than the particle size of the hot-melt organopolysiloxane fine particles, which are the component (A), a good silicone-filler matrix can be formed during melting. This improves the flexibility and mechanical strength of the cured product. In addition, since it does not substantially contain coarse particles, good gap-filling properties can also be achieved.

[0094] Furthermore, in order to impart other functions to the cured product obtained by using the composition, a white pigment, a thermally conductive filler, an electrically conductive filler, or a fluorescent material may be blended in. Also, in order to improve the stress relaxation properties of the cured product, an organic filler such as silicone elastomer fine particles may be blended in.

[0095] The white pigment is a component that imparts whiteness to the cured product and improves light reflectivity, and the cured product obtained by curing the composition by blending the component can be used as a light reflector for light emitting / optical devices. Examples of the white pigment include metal oxides such as titanium oxide, aluminum oxide, zinc oxide, zirconium oxide, and magnesium oxide; hollow fillers such as glass balloons and glass beads; and other materials such as barium sulfate, zinc sulfate, barium titanate, aluminum nitride, boron nitride, and antimony oxide. Titanium oxide is preferred because of its high light reflectance and hiding power. Aluminum oxide, zinc oxide, and barium titanate are preferred because of their high light reflectance in the UV region. The average particle size and shape of the white pigment are not limited, but the average particle size is preferably within the range of 0.05 to 10.0 μm, or 0.1 to 5.0 μm. The white pigment may be surface-treated with a silane coupling agent, silica, aluminum oxide, or the like.

[0096] The thermally conductive filler or the conductive filler is added for the purpose of imparting thermal conductivity / conductivity (electrical conductivity) to the cured product, and specific examples thereof include fine metal powders such as gold, silver, nickel, copper, and aluminum; fine powders of ceramics, glass, quartz, organic resins, and the like, on whose surfaces metals such as gold, silver, nickel, and copper are vapor-deposited or plated; metal compounds such as aluminum oxide, magnesium oxide, aluminum nitride, boron nitride, and zinc oxide; graphite, and mixtures of two or more of these. When electrical insulation is required for the composition, metal oxide powders or metal nitride powders are preferred, and aluminum oxide powder, zinc oxide powder, and aluminum nitride powder are particularly preferred, and these may be used in combination with each other in terms of type, particle size, particle shape, and the like according to the requirements for thermal conductivity / conductivity.

[0097] The phosphor is a component that is blended to convert the wavelength of light emitted from a light source (optical semiconductor element) when the cured product is used as a wavelength conversion material. There are no particular limitations on the phosphor, and examples of the phosphor include yellow, red, green, and blue light-emitting phosphors made of oxide-based phosphors, oxynitride-based phosphors, nitride-based phosphors, sulfide-based phosphors, oxysulfide-based phosphors, etc., which are widely used in light-emitting diodes (LEDs).

[0098] Examples of silicone fine particles include non-reactive silicone resin fine particles and silicone elastomer fine particles, with silicone elastomer fine particles being preferred from the standpoint of improving the flexibility or stress relaxation properties of the cured product.

[0099] Silicone elastomer microparticles are crosslinked products of linear diorganopolysiloxanes mainly composed of diorganosiloxy units (D units). Silicone elastomer microparticles can be prepared by crosslinking diorganopolysiloxanes by hydrosilylation reaction or condensation reaction of silanol groups, and can be preferably obtained by crosslinking an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at the side chain or end with a diorganopolysiloxane having unsaturated hydrocarbon groups such as alkenyl groups at the side chain or end under a hydrosilylation reaction catalyst. Silicone elastomer microparticles can take various shapes such as spherical, flat, and irregular, but from the viewpoint of dispersibility, spherical is preferable, and among them, true sphere is more preferable. Examples of commercially available silicone elastomer microparticles include "Trefil E Series" and "EP Powder Series" manufactured by Toray Dow Corning Co., Ltd., and "KMP Series" manufactured by Shin-Etsu Chemical Co., Ltd.

[0100] For the purpose of stably blending the functional filler as described above in the present composition, the filler may be surface-treated using a specific surface treatment agent in an amount of 0.1 to 2.0 mass%, 0.1 to 1.0 mass%, or 0.2 to 0.8 mass% relative to the total mass of component (B). Examples of such surface treatment agents include methylhydrogenpolysiloxane, silicone resin, metal soap, silane coupling agent, perfluoroalkylsilane, and fluorine compounds such as perfluoroalkyl phosphate salt.

[0101] Although the content of component (B) is not limited, the content of component (B) in the composition of the present invention is preferably within the range of 10 to 40 volume % of the total composition, more preferably 10 to 30 volume %, because the hardness and mechanical strength of the resulting cured product are excellent. If the content of component (B) is greater than the upper limit, the resulting cured product tends to be hard, and the maximum torque value obtained by measuring the MDR of the composition tends to be high, which may make the composition inappropriate for solving the problems of the present invention.

[0102] [(C) component] The component (C) is a curing agent for curing the component (A), and is not limited as long as it can cure the component (A), but is preferably one or more curing agents selected from the following (c1) or (c2). Two or more of these curing agents may be used in combination, and for example, the curing system may contain both the components (c1) and (c2). (c1) Organic peroxide (c2) an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in the molecule and a hydrosilylation reaction catalyst;

[0103] (c1) The organic peroxide is a component that cures the above-mentioned component (A) when heated. Examples of the organic peroxide include alkyl peroxides, diacyl peroxides, ester peroxides, and carbonate peroxides.

[0104] Examples of alkyl peroxides include dicumyl peroxide, di-tert-butyl peroxide, di-tert-butylcumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, tert-butylcumyl, 1,3-bis(tert-butylperoxyisopropyl)benzene, and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane.

[0105] Examples of diacyl peroxides include benzoyl peroxide, lauroyl peroxide, and decanoyl peroxide.

[0106] Examples of peroxy esters include 1,1,3,3-tetramethylbutyl peroxy neodecanoate, α-cumyl peroxy neodecanoate, tert-butyl peroxy neodecanoate, tert-butyl peroxy neoheptanoate, tert-butyl peroxy pivalate, tert-hexyl peroxy pivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, and tert-amyl peroxy-2-ethylhexanoate. , tert-butylperoxy-2-ethylhexanoate, tert-butylperoxyisobutyrate, di-tert-butylperoxyhexahydroterephthalate, tert-amylperoxy-3,5,5-trimethylhexanoate, tert-butylperoxy-3,5,5-trimethylhexanoate, tert-butylperoxyacetate, tert-butylperoxybenzoate, and di-butylperoxytrimethyladipate are examples.

[0107] Examples of peroxycarbonates include di-3-methoxybutyl peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, diisopropyl peroxycarbonate, tert-butylperoxyisopropyl carbonate, di(4-tert-butylcyclohexyl) peroxydicarbonate, dicetyl peroxydicarbonate, and dimyristyl peroxydicarbonate.

[0108] The organic peroxide preferably has a half-life of 10 hours at a temperature of 90° C. or higher, or 95° C. or higher. Examples of such organic peroxides include dicumyl peroxide, di-t-butyl peroxide, di-t-hexyl peroxide, t-butylcumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 1,3-bis(tert-butylperoxyisopropyl)benzene, di-(2-t-butylperoxyisopropyl)benzene, and 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane.

[0109] The content of (c1) organic peroxide is not limited, but is preferably within a range of 0.05 to 10 parts by mass, or 0.10 to 5.0 parts by mass, per 100 parts by mass of (A).

[0110] (c2) An organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms per molecule and a hydrosilylation catalyst are components that cure the composition by undergoing an addition reaction (hydrosilylation reaction) between the organohydrogenpolysiloxane, which is a crosslinking agent, and the carbon-carbon double bonds in component (A) in the presence of the hydrosilylation catalyst.

[0111] The organohydrogenpolysiloxane which is a part of the component (c2) is not particularly limited in its molecular structure, and may be one or more selected from the linear organohydrogenpolysiloxanes exemplified as the component (a2), particularly the linear organohydrogenpolysiloxanes exemplified as the component (a2-1), and the organohydrogenpolysiloxane resins exemplified as the component (a2-2), or mixtures thereof. In particular, linear organohydrogenpolysiloxanes having silicon-bonded hydrogen atoms at least at both ends of the molecular chain and a siloxane polymerization degree of 2 to 200, preferably 3 to 100, are preferred, and preferred examples thereof are as follows. In the formula, Me and Ph represent a methyl group and a phenyl group, respectively. Ph2Si(OSiMe2H)2, i.e., Ph 0.67 Me 1.33 H 0.67 SiO 0.67 HMe2SiO(Me2SiO) 20 SiMe2H, i.e., Me 2.00 H 0.09 SiO 0.95 HMe2SiO(Me2SiO) 55 SiMe2H, i.e., Me 2.00 H 0.04 SiO 0.98 PhSi(OSiMe2H)3, i.e., Ph 0.25 Me 1.50 H 0.75 SiO 0.75 (HMeSiO 1 / 2 ) 0.6 (PhSiO 3 / 2 ) 0.4 , i.e., Ph 0.40 Me 1.20 H 0.60 SiO 0.90

[0112] The content of the organohydrogenpolysiloxane which is part of component (c2) is an amount sufficient to cure the curable granular silicone composition of the present invention, and is an amount such that the molar ratio of silicon-bonded hydrogen atoms in the organohydrogenpolysiloxane to the curing reactive functional groups containing a carbon-carbon double bond in component (A) (for example, alkenyl groups such as vinyl groups) is 0.5 or more, preferably in the range of 0.5 to 20. In particular, when component (c2) contains the above-mentioned organohydrogenpolysiloxane resin, it is preferably an amount such that the molar ratio of silicon-bonded hydrogen atoms in the organohydrogenpolysiloxane resin to the curing reactive functional groups containing a carbon-carbon double bond in component (A) is in the range of 0.5 to 20, or in the range of 1.0 to 10.

[0113] Examples of the hydrosilylation catalyst, which is a part of component (c2), include platinum-based catalysts, rhodium-based catalysts, and palladium-based catalysts, with platinum-based catalysts being preferred because they can significantly accelerate the curing of the composition. Examples of platinum-based catalysts include platinum fine powder, chloroplatinic acid, alcohol solutions of chloroplatinic acid, platinum-alkenylsiloxane complexes, platinum-olefin complexes, platinum-carbonyl complexes, and catalysts in which these platinum-based catalysts are dispersed or encapsulated in thermoplastic resins such as silicone resins, polycarbonate resins, and acrylic resins, with platinum-alkenylsiloxane complexes being particularly preferred. Examples of the alkenylsiloxane include 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, alkenylsiloxanes in which a part of the methyl groups of these alkenylsiloxanes is replaced with an ethyl group, a phenyl group, or the like, and alkenylsiloxanes in which the vinyl groups of these alkenylsiloxanes are replaced with an allyl group, a hexenyl group, or the like. In particular, since the stability of this platinum-alkenylsiloxane complex is good, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane is preferred, and it is preferred to add the complex in the form of an alkenylsiloxane solution. In addition, from the viewpoint of improving the handling and workability and the pot life of the composition, a platinum-containing hydrosilylation reaction catalyst in the form of fine particles dispersed or encapsulated in a thermoplastic resin may be used. As a catalyst for promoting the hydrosilylation reaction, a non-platinum metal catalyst such as iron, ruthenium, or iron / cobalt may be used.

[0114] The amount of the hydrosilylation reaction catalyst, which is part of component (c2), added is preferably an amount such that the metal atoms are in the range of 0.01 to 500 ppm, 0.01 to 100 ppm, or 0.01 to 50 ppm, by mass, relative to the entire composition.

[0115] Particularly preferred (c2) components are (c2-1) Contains at least a dimethylorganopolysiloxane having silicon-bonded hydrogen atoms at both molecular chain terminals and a hydrosilylation reaction catalyst.

[0116] The curable granular silicone composition of the present invention comprises the above-mentioned components (A) to (C). From the standpoint of further improving the melting properties, it is possible and preferable to add (D) hot-melt particles having a dropping point of 50°C or higher and a melt viscosity of 10 Pas or less as measured with a rotational viscometer at 150°C.

[0117] As long as the dropping point conditions and the kinetic viscosity conditions at 150°C are satisfied, the type of component (D) is not particularly limited, and one or more selected from various hot-melt synthetic resins, waxes, fatty acid metal salts, etc. can be used. The component (D) exhibits low kinetic viscosity at high temperatures (150°C) and forms a molten material with excellent fluidity. Furthermore, by using the above components (A) to (C) in combination, the component (D) in the molten material of this composition spreads quickly throughout the entire composition at high temperatures, thereby reducing the viscosity of the substrate surface to which the molten composition is applied and the entire composition, and also rapidly reducing the surface friction of the substrate and the molten composition, thereby significantly increasing the fluidity of the entire composition. Therefore, the viscosity and fluidity of the molten composition can be greatly improved by adding only a small amount of the component (D) relative to the total amount of other components.

[0118] As long as the above-mentioned dropping point and kinetic viscosity conditions during melting are satisfied, component (D) may be a petroleum wax such as paraffin, but from the viewpoint of the technical effects of the present invention, it is preferable that the component (D) is a hot-melt component made of a fatty acid metal salt, and particularly preferable are metal salts of higher fatty acids such as stearic acid, palmitic acid, oleic acid, isononanoic acid, etc. Here, the type of the fatty acid metal salt is not particularly limited, but suitable examples include alkali metal salts such as lithium, sodium, potassium, etc.; alkaline earth metal salts such as magnesium, calcium, barium, etc.; and zinc salts.

[0119] Particularly preferred as component (D) is a fatty acid metal salt (D0) having a free fatty acid content of 5.0% or less, more preferably 4.0% or less, and more preferably 0.05 to 3.5%. An example of such component (D0) is at least one metal stearate. From the viewpoint of the technical effect of the present invention, it is preferred that component (D0) is substantially composed of one or more metal stearate salts, and it is most preferred to use a hot melt component having a melting point of 150°C or less selected from calcium stearate (melting point 150°C), zinc stearate (melting point 120°C), and magnesium stearate (melting point 130°C).

[0120] The amount of the (D) component used is in the range of 0.01 to 5.0 parts by mass, and may be 0.01 to 3.5 parts by mass, or 0.01 to 3.0 parts by mass, when the entire composition is taken as 100 parts by mass. If the amount of the (D) component used exceeds the upper limit, the adhesiveness and mechanical strength of the cured product obtained from the curable silicone composition for transfer molding of the present invention may be insufficient. If the amount of the (D) component used is less than the lower limit, sufficient fluidity may not be achieved when heated and melted.

[0121] The composition may also contain other optional components such as a cure retarder and an adhesion promoter, provided that the object of the present invention is not impaired.

[0122] Examples of the curing retarder include alkyne alcohols such as 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, and 1-ethynyl-1-cyclohexanol; enyne compounds such as 3-methyl-3-penten-1-yne and 3,5-dimethyl-3-hexen-1-yne; alkenyl-containing low molecular weight siloxanes such as tetramethyltetravinylcyclotetrasiloxane and tetramethyltetrahexenylcyclotetrasiloxane; and alkynyloxysilanes such as methyl-tris(1,1-dimethylpropynyloxy)silane and vinyl-tris(1,1-dimethylpropynyloxy)silane. The content of this curing retarder is not limited, but is preferably within the range of 10 to 10,000 ppm by mass with respect to the present composition.

[0123] As the adhesion promoter, an organic silicon compound having at least one alkoxy group bonded to a silicon atom in one molecule is preferred. Examples of this alkoxy group include methoxy, ethoxy, propoxy, butoxy, and methoxyethoxy groups, and particularly preferred is methoxy. Examples of groups bonded to silicon atoms other than the alkoxy group in the organic silicon compound include halogen-substituted or unsubstituted monovalent hydrocarbon groups such as alkyl groups, alkenyl groups, aryl groups, aralkyl groups, and halogenated alkyl groups; glycidoxyalkyl groups such as 3-glycidoxypropyl and 4-glycidoxybutyl groups; epoxycyclohexylalkyl groups such as 2-(3,4-epoxycyclohexyl)ethyl and 3-(3,4-epoxycyclohexyl)propyl groups; epoxyalkyl groups such as 3,4-epoxybutyl and 7,8-epoxyoctyl groups; acrylic group-containing monovalent organic groups such as 3-methacryloxypropyl groups; and hydrogen atoms. The organosilicon compound preferably has a group capable of reacting with the alkenyl group or silicon-bonded hydrogen atom in the composition, and more specifically, preferably has a silicon-bonded hydrogen atom or an alkenyl group.In addition, since it can provide good adhesion to various substrates, the organosilicon compound preferably has at least one epoxy-containing monovalent organic group in one molecule.Examples of such organosilicon compounds include organosilane compounds, organosiloxane oligomers, and alkyl silicates.Examples of the molecular structure of the organosiloxane oligomer or alkyl silicate include linear, partially branched linear, branched, cyclic, and net-like, and in particular, linear, branched, and net-like are preferred.Examples of the organosilicon compounds include silane compounds such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane; siloxane compounds having at least one silicon-bonded alkenyl group or one silicon-bonded hydrogen atom, and at least one silicon-bonded alkoxy group in one molecule; a mixture of a silane compound or siloxane compound having at least one silicon-bonded alkoxy group and a siloxane compound having at least one silicon-bonded hydroxy group and at least one silicon-bonded alkenyl group in one molecule; a reaction mixture of an amino group-containing organoalkoxysilane and an epoxy group-containing organoalkoxysilane; an organic compound having at least two alkoxysilyl groups in one molecule and containing a bond other than a silicon-oxygen bond between the silyl groups; a n Si(OR b ) 4-n (In the formula, R a is a monovalent epoxy-containing organic group, and R b is an alkyl group having 1 to 6 carbon atoms or a hydrogen atom; and n is a number ranging from 1 to 3. Examples of the adhesion promoter include epoxy group-containing silanes represented by the formula (I) or partial hydrolysis condensates thereof, a reaction mixture of a vinyl group-containing siloxane oligomer (including those with a chain or cyclic structure) and an epoxy group-containing trialkoxysilane, methyl polysilicate, ethyl polysilicate, and epoxy group-containing ethyl polysilicate. The adhesion promoter is preferably a low-viscosity liquid, and although there are no limitations on its viscosity, it is preferably within the range of 1 to 500 mPa·s at 25°C. The content of the adhesion promoter is also not limited, but is preferably within the range of 0.01 to 10 parts by mass per 100 parts by mass of the total of the present composition.

[0124] Furthermore, the composition may contain other optional components, such as heat resistance agents such as iron oxide (red oxide), cerium oxide, cerium dimethylsilanolate, fatty acid cerium salts, cerium hydroxide, and zirconium compounds, as well as dyes, pigments other than white, and flame retardants, so long as the object of the present invention is not impaired.

[0125] [Form of composition] The curable silicone composition for transfer molding according to the present invention may be a non-fluid solid at 25° C., or may be in a paste or semi-solid state. Since the curable silicone composition is used for transfer molding, it is preferable that the composition is a solid having a softening point of 100° C. or less and melting property upon heating. On the other hand, the composition may be in a paste or semi-solid state, and preferably has the property of increasing fluidity and rapidly decreasing viscosity upon heating.

[0126] When the present composition is used as a hot-melt curable silicone composition, it is preferably a solid that is non-fluid and has heat melting properties at 25°C, and may be molded into granules or pellets for use. A granular composition can be easily obtained by granulating only the components constituting the curable silicone composition by mixing them under a temperature condition not exceeding 50°C, and it is preferable to further mold the granular curable silicone composition into pellets for use. When making into pellets, the sheet-shaped molded body may be punched or cut to be molded.

[0127] The pellet-shaped composition is obtained by tableting the composition, and has excellent handling and hardening properties. The "pellet" may also be called a "tablet". The shape of the pellet is not limited, but is usually spherical, elliptical, or cylindrical. The size of the pellet is not limited, but has an average particle diameter or circle equivalent diameter of, for example, 500 μm or more.

[0128] The present composition can be handled in the form of pellets at room temperature, and is preferably a non-fluid solid at 25°C. Here, non-fluidity means that the composition does not deform or flow in an unloaded state, and preferably does not deform or flow in an unloaded state at 25°C when molded into pellets, tablets, or the like. Such non-fluidity can be evaluated, for example, by placing the molded composition on a hot plate at 25°C and not substantially deforming or flowing even when no load or a certain load is applied. If the composition is non-fluid at 25°C, the shape retention at that temperature is good and the surface adhesion is low.

[0129] The softening point of the present composition is preferably 100° C. or lower. Such a softening point means the temperature at which, when a load of 100 grams is applied to a hot plate for 10 seconds and the deformation of the composition is measured after the load is removed, the deformation in the height direction is 1 mm or more.

[0130] The viscosity of the composition tends to decrease rapidly under high temperature and high pressure (i.e., during the molding process), and it is preferable to use a value measured under similar high temperature and high pressure as a useful melt viscosity value. Therefore, it is preferable to measure the melt viscosity of the composition under high pressure using a Koka-shiki flow tester (manufactured by Shimadzu Corporation) rather than measuring it with a rotational viscometer such as a rheometer. Specifically, it is preferable that the melt viscosity of the composition at 150°C is 200 Pa·s or less, more preferably 150 or less. This is because the composition has good adhesion to the substrate after being cooled to 25°C after being hot melted.

[0131] When the present composition is a hot-melt composition or a granular composition, it can be produced by powder mixing components (A) to (C) and any other components at a temperature of less than 50° C. There are no limitations on the powder mixer used in the present production method, and examples include a single-screw or twin-screw continuous mixer, a twin roll, a Ross mixer, a Hobart mixer, a dental mixer, a planetary mixer, a kneader mixer, a laboratory miller, a small grinder, and a Henschel mixer, with a laboratory miller and a Henschel mixer being preferred.

[0132] The curable silicone composition for transfer molding according to the present invention may be in a paste or semi-solid state, and is preferably a paste or semi-solid composition with poor fluidity. The composition can be obtained by uniformly mixing components (A) to (C) and any other optional components using a mechanical mixer such as a Ross mixer or a Hobart mixer among the above mixers.

[0133] When the composition is in a paste form at 25° C., the viscosity at 25° C. is not particularly limited, but is preferably in the range of 5 to 200 Pa·s, more preferably in the range of 5 to 120 Pa·s, and particularly preferably in the range of 10 to 80 Pa·s. This is because, when the viscosity is equal to or higher than the lower limit of the above range, the generation of burrs during molding of the resulting composition is suppressed, whereas, when the viscosity is equal to or lower than the upper limit of the above range, the handling and workability of the resulting composition is good.

[0134] [Method of molding the cured product] The present composition can be cured by a method comprising at least the following steps (I) to (III). (I) heating the composition to 100° C. or higher to melt it; (II) a step of injecting the curable silicone composition obtained in step (I) into a mold, or a step of spreading the curable silicone composition obtained in step (I) around the mold by clamping the mold; and (III) A step of curing the curable silicone composition injected in the step (II)

[0135] The above-mentioned process is applicable to general molding machines such as a transfer molding machine, a compression molding machine, an injection molding machine, an auxiliary ram type molding machine, a slide type molding machine, a double ram type molding machine, or a low-pressure encapsulation molding machine, but the composition of the present invention can be suitably used for the purpose of obtaining a cured product by transfer molding.

[0136] Finally, in step (III), the curable silicone composition injected (applied) in step (II) is cured. When (c1) an organic peroxide is used as component (C), the heating temperature is preferably 150°C or higher, or 170°C or higher, and when (c2) an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in the molecule and a hydrosilylation reaction catalyst are used, the heating temperature is preferably 100°C or higher, or 130°C or higher.

[0137] Since the composition is suitable as a light reflector for light-emitting / optical devices or a protective material for semiconductors, etc., it is preferable that the type D durometer hardness at 25° C. of the cured product obtained by curing the composition is not less than 20. The type D durometer hardness is determined using a type D durometer in accordance with JIS K 6253-1997 "Testing method for hardness of vulcanized rubber and thermoplastic rubber."

[0138] [Use of the composition] This composition is a material for transfer molding, and is particularly suitable as a sealing material for semiconductors and the like using an overmolding method in which a substrate and a cured product are integrated during molding. That is, the curable silicone composition for transfer molding of the present invention preferably has hot melt properties, is excellent in handling and curing properties when melted (hot melt), and the cured product molded by transfer molding has low modulus and flexibility even at high temperatures and has excellent stress relaxation properties, so that the molded product is unlikely to warp or have defects during integral molding, and the cured product after transfer molding has excellent demolding properties, so that it is usefully used for semiconductor members such as light reflectors for light-emitting / optical devices and optical semiconductors having the cured product. Furthermore, since the cured product has excellent mechanical properties, it is suitable as a sealant for semiconductors; a sealant for power semiconductors such as SiC and GaN; and an adhesive, potting agent, protective agent, and coating agent for electrical and electronic devices. In particular, it is suitable for use as a sealant for semiconductors using an overmolding method during molding.

[0139] [Uses of the cured product] The use of the cured product of the present invention is not particularly limited as long as it is obtained by transfer molding, but the cured product molded by transfer molding has a low modulus and flexibility even at high temperatures, and has excellent stress relaxation properties, so that the molded product is less likely to warp or have defects. Therefore, the cured product obtained by curing the present composition can be suitably used as a member for semiconductor devices, and can be suitably used as a sealing material for semiconductor elements, IC chips, etc., and as an adhesive / bonding material for semiconductor devices.

[0140] The semiconductor device having a member made of the cured product of the present invention is not particularly limited, but is preferably a light-emitting semiconductor device that is a light-emitting / optical device. EXAMPLES

[0141] The hot-melt curable silicone composition of the present invention and its manufacturing method will be described in detail with reference to examples and comparative examples. In the formula, Me, Ph, and Vi represent a methyl group, a phenyl group, and a vinyl group, respectively. In addition, the softening point, curing behavior, moldability, and warpage of molded products of the curable silicone compositions of each example and comparative example were measured by the following methods. The results are shown in Table 1.

[0142] [Softening point of curable granular silicone composition] The curable granular silicone composition was molded into a cylindrical pellet of φ14 mm×22 mm. The pellet was placed on a hot plate set at 25° C. to 100° C., and pressed from above with a load of 100 grams for 10 seconds. After removing the load, the deformation of the pellet was measured. The temperature at which the deformation in the height direction became 1 mm or more was taken as the softening point.

[0143] [Curing behavior of curable silicone composition] The curable silicone composition was vulcanized for 600 seconds at the molding temperature (150°C) and measured using a curastometer (PREMIER MDR manufactured by Alpha Technologies) according to the method specified in JIS K 6300-2:2001 "Unvulcanized rubber - Physical properties - Part 2: Determination of vulcanization properties using a vibration vulcanization tester". For the measurement, if the curable silicone composition is hot melt, it is molded into a cylindrical pellet, and about 7 g of it is placed on the lower die, and if it is liquid, about 7 g is placed as is, and the measurement starts when the upper die is closed. For the measurement, an R-type die for rubber is used, and the measurement is performed with an amplitude angle of 0.53°, a vibration frequency of 100 times / min, and a maximum torque range of 230 kgf·cm. The measurement results show the stored torque and loss torque, and the ratio (stored torque / loss torque) is read as tan δ at the time of curing.

[0144] [Moldability of the curable silicone composition] The curable silicone composition was molded into a silver-plated copper lead frame using a transfer molding machine to produce a molded product measuring 35mm long x 25mm wide x 1mm high. The molding conditions were a mold temperature of 150°C and a mold clamping time of 120 seconds, and moldability was confirmed without applying any release agent to the upper or lower molds of the molding machine. After the molding cycle was completed, the results were evaluated as OK if the molded product could be smoothly removed from the mold, and NG if it stuck to the mold and could not be removed. Demoldability was evaluated under harsh conditions by using silver, a difficult-to-adhere material, as the adherend.

[0145] [Warping of molded products] The curable silicone composition was molded into an integral shape by heating it for 2 hours at 150°C using a hot press on an aluminum plate measuring 60 mm x 60 mm x 0.4 mm. One side of the molded product obtained was fixed to a horizontal desk with tape, and the distance the other side rose from the desk was measured with a ruler, and this was taken as the warpage value of the molded product.

[0146] Organopolysiloxane resins or crosslinked organopolysiloxanes containing a hydrosilylation catalyst were prepared by the methods shown in Reference Examples 1 to 6 below, and the presence or absence of hot melt properties was evaluated based on the presence or absence of softening point / melt viscosity. Also, organopolysiloxane resin fine particles were prepared by the methods shown in Reference Examples 3 to 6. In the Reference Examples, 1,1,3,3-tetramethyl-1,3-divinyldisiloxane used in the platinum complex, which is a hydrosilylation catalyst, is referred to as "1,3-divinyltetramethyldisiloxane."

[0147] [Reference example 1] In a 1 L flask, at 25°C, a white solid was obtained with the average unit formula: (PhSiO 3 / 2 ) 0.80 (Me2ViSiO 1 / 2 ) 0.20 270.5 g of a 55% by mass toluene solution of a resinous organopolysiloxane represented by the formula: HMe2SiO(Ph2SiO)SiMe2H 21.3 g (an amount such that there are 0.5 moles of silicon-bonded hydrogen atoms in this component per mole of vinyl groups in the resinous organopolysiloxane) of diphenylsiloxane capped with dimethylhydrogensiloxy groups at both molecular chain ends and having a viscosity of 5 mPa s (silicon-bonded hydrogen atom content = 0.6% by mass), and 0.43 g (an amount such that platinum metal would be 10 ppm by mass in the liquid mixture) of a 1,3-divinyltetramethyldisiloxane solution of platinum 1,3-divinyltetramethyldisiloxane complex (platinum metal content = approximately 4000 ppm) were added and stirred uniformly at room temperature. The temperature in the flask was then raised to 100°C in an oil bath, and the mixture was stirred under toluene reflux for 2 hours to prepare a toluene solution of organosiloxane crosslinked product (1) that was made up of a resinous organosiloxane derived from the resinous organopolysiloxane and a linear organosiloxane derived from the diphenylsiloxane, and had a vinyl group that was not involved in the reaction. When this organosiloxane crosslinked product (1) was analyzed by FT-IR, no peaks of silicon-bonded hydrogen atoms were observed. The softening point of this organosiloxane crosslinked product (1) was 75°C, and its melt viscosity at 100°C was 700 Pa·s.

[0148] [Reference example 2] In a 1 L flask, at 25°C, a white solid was obtained with the average unit formula: (Me2ViSiO 1 / 2 ) 0.05 (Me3SiO 1 / 2 ) 0.39 (SiO 4 / 2 ) 0.56 (HO 1 / 2 ) 0.02 270.5 g of a 55 mass % xylene solution of an organopolysiloxane resin represented by the formula (1) and 0.375 g of a 1,3-divinyltetramethyldisiloxane solution of a platinum 1,3-divinyltetramethyldisiloxane complex (platinum metal content = approximately 4000 ppm) were added and stirred uniformly at room temperature (25°C) to prepare a xylene solution of organopolysiloxane resin (2) containing 10 ppm by mass as platinum metal. Furthermore, this organopolysiloxane resin (2) did not soften / melt even when heated to 200°C, and did not have hot melt properties.

[0149] [Reference example 3] In a 1 L flask, at 25°C, a white solid was obtained with the average unit formula: (Me3SiO 1 / 2 ) 0.44 (SiO 4 / 2 ) 0.56 (HO 1 / 2 ) 0.02 270.5 g of a 55 mass % xylene solution of an organopolysiloxane resin represented by the formula (1) and 0.375 g of a 1,3-divinyltetramethyldisiloxane solution of a platinum 1,3-divinyltetramethyldisiloxane complex (platinum metal content = about 4000 ppm) were added and stirred uniformly at room temperature (25°C) to prepare a xylene solution of organopolysiloxane resin (3) containing 10 ppm by mass as platinum metal. Furthermore, this organopolysiloxane resin (3) did not soften / melt even when heated to 200°C, and did not have hot melt properties.

[0150] [Reference Example 4: Hot-melt organopolysiloxane resin microparticles (1)] The toluene solution of the organosiloxane crosslinked product (1) prepared in Reference Example 1 was atomized by spray drying at 40° C. while removing the toluene, to prepare spherical hot-melt silicone microparticles (1). When the microparticles were observed with an optical microscope, the particle diameter was 5 to 10 μm, and the average particle diameter was 7.5 μm.

[0151] [Reference Example 5: Non-hot melt organopolysiloxane resin fine particles (2)] The xylene solution of organopolysiloxane resin (2) prepared in Reference Example 1 was granulated at 50° C. by a spray method using a spray dryer while removing the xylene, to prepare spherical non-hot melt organopolysiloxane resin microparticles (2). When the microparticles were observed under an optical microscope, the particle diameter was 5 to 10 μm, and the average particle diameter was 6.9 μm.

[0152] [Reference Example 6: Non-hot melt organopolysiloxane resin fine particles (3)] The xylene solution of organopolysiloxane resin (3) prepared in Reference Example 2 was granulated at 50° C. by a spray method using a spray dryer while removing the xylene, to prepare spherical non-hot melt organopolysiloxane resin microparticles (3). When the microparticles were observed under an optical microscope, the particle diameter was 5 to 10 μm, and the average particle diameter was 7.4 μm.

[0153] [Example 1] Hot melt silicone microparticles (1) 73.1 g, formula: HMe2SiO(Ph2SiO)SiMe2H The mass of the diphenylsiloxane is 9.5 g and the viscosity is 1,000 mPa s. The mass of the diphenylsiloxane is 9.5 g and the viscosity is 5 mPa s. The mass of the diphenylsiloxane is 9.5 g and the viscosity is 1,000 mPa s. Average formula Me2ViSiO(MePhSiO) 17.5 SiMe2Vi Methylphenylpolysiloxane terminated at both ends of the molecular chain with dimethylvinylsiloxy groups (vinyl group content = 2.1% by mass) {The amount of silicon-bonded hydrogen atoms in the diphenylsiloxane is 0.9 moles for 1.0 mole of vinyl groups in the silicone fine particles (1) and the methylphenyl polysiloxane blocked by dimethylvinylsiloxy groups at both ends of the molecular chain}, 1-ethynyl-1-cyclohexanol (amount of 300 ppm by mass relative to the composition), 24.0 g of fused silica (SP60 manufactured by Nippon Steel Materials Micron Co., Ltd.) with an average particle size of 2.5 μm, and 30.0 g of fumed silica (AEROSIL50 manufactured by Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm are put into a small grinder at once, and stirred at room temperature (25 ° C) for 1 minute to prepare a uniform curable granular silicone composition.In addition, the measurement results of the softening point of this composition are shown in Table 1.

[0154] [Example 2] Hot melt silicone microparticles (1) 89.3 g, formula: HMe2SiO(Ph2SiO)SiMe2H 10.7 g of diphenylsiloxane terminated at both ends with dimethylhydrogensiloxy groups and having a viscosity of 5 mPa s (content of silicon-bonded hydrogen atoms = 0.6% by mass), {The amount of silicon-bonded hydrogen atoms in the diphenylsiloxane is 0.9 moles relative to 1.0 mole of vinyl group in silicone fine particles (1)}, 1-ethynyl-1-cyclohexanol (the amount of 300 ppm by mass relative to this composition), 98.0 g of titanium oxide (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) with an average particle size of 0.5 μm, and 4.0 g of fumed silica (AEROSIL50 manufactured by Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm are put into a small grinder at once, and stirred at room temperature (25 ° C) for 1 minute to prepare a uniform curable granular silicone composition.In addition, the measurement results of the softening point of this composition are shown in Table 1.

[0155] [Example 3] Average unit formula: (MeViSiO 2 / 2 ) 0.25 (PhSiO 3 / 2 ) 0.75 64.1 g of methylvinylphenylpolysiloxane represented by the formula: The viscosity is 1,000 mPa s. Average formula Me2ViSiO(MePhSiO) 17.5 SiMe2Vi 10.5 g of methylphenylpolysiloxane terminated at both ends of the molecular chain with dimethylvinylsiloxy groups (vinyl group content = 2.1% by mass) (MeViSiO)4 1.0 g of 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane represented by the formula: Formula:(HMe2SiO)2SiPh2 22.2g of 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane represented by the formula (MeHSiO 1 / 2 ) 0.6 (PhSiO 3 / 2 ) 0.4 2.3 g of methylphenylpolysiloxane containing silicon-bonded hydrogen atoms represented by the formula: {An amount such that the amount of SiH groups in the silicon-bonded hydrogen atom-containing polysiloxane is 0.93 moles per mole of vinyl groups in the vinyl group-containing polysiloxane} 1,3-divinyl-1,1,3,3-tetramethyldisiloxane solution of platinum (an amount equivalent to 3.5 ppm by mass of platinum metal relative to the composition), 1-ethynyl-1-cyclohexanol (an amount equivalent to 200 ppm by mass of the composition), titanium oxide with an average primary particle size of 0.2 μm (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) 25 g The above ingredients were mixed uniformly using a mechanical force (Hobart mixer) to prepare a curable silicone composition that was in a paste form at room temperature. The measurement results of the property values ​​of this composition are shown in Table 1. Note that since this composition was in a paste form, the softening point was not measured (N / A).

[0156] [Example 4] Average unit formula: (MeViSiO 2 / 2 ) 0.25 (PhSiO 3 / 2 ) 0.75 57.3 g of methylvinylphenylpolysiloxane represented by the formula: Average unit formula: (MeViSiO 2 / 2 ) 0.68 (PhSiO 3 / 2 ) 0.32 5.0 g of methylvinylphenylpolysiloxane represented by the formula: The viscosity is 1,000 mPa s. Average formula Me2ViSiO(MePhSiO) 17.5 SiMe2Vi 9.0 g of methylphenylpolysiloxane terminated at both ends of the molecular chain with dimethylvinylsiloxy groups (vinyl group content = 2.1% by mass) (MeViSiO)4 1.1 g of 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane represented by the formula: Formula:(HMe2SiO)2SiPh2 24.4g of 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane represented by the formula (MeHSiO 1 / 2 ) 0.6 (PhSiO 3 / 2 ) 0.4 3.2g of methylphenylpolysiloxane containing silicon-bonded hydrogen atoms represented by the formula: {An amount such that the amount of SiH groups in the silicon-bonded hydrogen atom-containing polysiloxane is 0.97 moles per mole of the total vinyl groups in the vinyl group-containing polysiloxane.} 1,3-divinyl-1,1,3,3-tetramethyldisiloxane solution of platinum (an amount equivalent to 3.5 ppm by mass of platinum metal relative to the composition), 1-ethynyl-1-cyclohexanol (an amount equivalent to 200 ppm by mass of the composition), titanium oxide with an average primary particle size of 0.2 μm (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) 43 g The above ingredients were mixed uniformly using a mechanical force (Hobart mixer) to prepare a curable silicone composition that was in a paste form at room temperature. The measurement results of the property values ​​of this composition are shown in Table 1. Note that since this composition was in a paste form, the softening point was not measured (N / A).

[0157] [Comparative Example 1] (a+c(pt)) Non-hot melt organopolysiloxane resin fine particles (3) (vinyl group content = 0 mass%) 55.3 g, (a+c(pt)) 13.8 g of non-hot melt organopolysiloxane resin fine particles (2) (vinyl group content = 1.91% by mass), Formula (b1): ViMe2SiO(Me2SiO) 800 SiViMe2 29.6 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 0.09% by mass), (c2(SiH)) formula: (HMeSiO 1 / 2 ) 0.67 (SiO 4 / 2 ) 0.33 1.1 g of organohydrogenpolysiloxane resin (content of silicon-bonded hydrogen atoms = 0.95% by mass) {an amount such that the organohydrogenpolysiloxane resin contains 1.1 moles of silicon-bonded hydrogen atoms per mole of vinyl groups in the organopolysiloxane resin fine particles (2) and the dimethylpolysiloxane terminally blocked with dimethylvinylsiloxy groups}, (d1) 232.6 g of alumina having an average particle size of 0.44 μm (AES-12 manufactured by Sumitomo Chemical Co., Ltd.); 1-ethynyl-1-cyclohexanol (in an amount equivalent to 1000 ppm by mass of the composition) was added all at once to a small grinder and stirred at room temperature (25°C) for 1 minute to prepare a uniform curable granular silicone composition. Additionally, the results of measuring the softening point and other properties of this composition are shown in Table 1.

[0158] [Comparative Example 2] Hot melt silicone microparticles (1) 89.3 g, formula: HMe2SiO(Ph2SiO)SiMe2H 10.7 g of diphenylsiloxane terminated at both ends with dimethylhydrogensiloxy groups and having a viscosity of 5 mPa s (content of silicon-bonded hydrogen atoms = 0.6% by mass), {The amount of silicon-bonded hydrogen atoms in the diphenylsiloxane is 0.9 moles relative to 1.0 mole of vinyl group in silicone fine particles (1)}, 1-ethynyl-1-cyclohexanol (the amount of 300 ppm by mass relative to this composition), 298.5 g of titanium oxide (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) with an average particle size of 0.5 μm, and 1.5 g of fumed silica (AEROSIL50 manufactured by Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm are put into a small grinder at once, and stirred at room temperature (25 ° C) for 1 minute to prepare a uniform curable granular silicone composition.In addition, the measurement results such as the softening point of this composition are shown in Table 1.

[0159] [Comparative Example 3] Hot melt silicone microparticles (1) 45.0 g, The viscosity is 20,000 mPa·s. Average formula Me2ViSiO(MePhSiO) 92 SiMe2Vi Methylphenylpolysiloxane terminated at both ends with dimethylvinylsiloxy groups (vinyl group content = 0.63% by mass) formula: HMe2SiO(Ph2SiO)SiMe2H 1.0 g of diphenylsiloxane terminated with dimethylhydrogensiloxy groups at both ends of the molecular chain (content of silicon-bonded hydrogen atoms = 0.6% by mass) with a viscosity of 5 mPa s, expressed as: average unit formula: (PhSiO 3 / 2 ) 0.4 (HMeSiO 1 / 2 ) 0.6 6.3 g of a branched-chain organopolysiloxane having two or more silicon-bonded hydrogen atoms in one molecule and a viscosity of 25 mPa s (content of silicon-bonded hydrogen atoms = 0.65% by mass). {The amount of silicon-bonded hydrogen atoms in the diphenylsiloxane and branched organopolysiloxane is 1.0 mole relative to 1.0 mole of vinyl group in silicone fine particles (1)}, 1-ethynyl-1-cyclohexanol (the amount of 300 ppm by mass relative to this composition), 98.0 g of titanium oxide (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) with an average particle size of 0.5 μm, and 4.0 g of fumed silica (AEROSIL50 manufactured by Nippon Aerosil Co., Ltd.) with an average particle size of 0.04 μm are put into a small grinder at once, and stirred at room temperature (25 ° C) for 1 minute to prepare a uniform curable granular silicone composition.In addition, the measurement results such as the softening point of this composition are shown in Table 1.

[0160] [Comparative Example 4] (a+c(pt)) 34.1 g of non-hot melt organopolysiloxane resin fine particles (2) (vinyl group content = 0 mass%), (a+c(pt)) 34.1 g of non-hot melt organopolysiloxane resin fine particles (1) (vinyl group content = 1.91% by mass), Formula (b2): ViMe2SiO(Me2SiO) 140 SiViMe2 14.5 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 0.44% by mass), Formula (b3): ViMe2SiO(Me2SiO) 300 SiViMe2 14.5 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 0.21% by mass), (c2(SiH)) formula: (HMeSiO 1 / 2 ) 0.67 (SiO 4 / 2 ) 0.33 Organohydrogenpolysiloxane resin (content of silicon-bonded hydrogen atoms = 0.95% by mass) represented by the formula: {an amount such that the organohydrogenpolysiloxane resin contains 1.1 moles of silicon-bonded hydrogen atoms per mole of vinyl groups in the organopolysiloxane resin fine particles (1) and the dimethylpolysiloxane terminally blocked with dimethylvinylsiloxy groups}, (d2) 142.6 g of titanium oxide having an average particle size of 0.5 μm (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.), (d3) 10.3 g of fumed silica having an average particle size of 0.04 μm (AEROSIL 50 manufactured by Nippon Aerosil Co., Ltd.), and 1-ethynyl-1-cyclohexanol (an amount equivalent to 1000 ppm by mass of the composition) were charged all at once into a small grinder and stirred for 1 minute at room temperature (25° C.) to prepare a uniform curable granular silicone composition. Additionally, the results of measuring the softening point and other properties of this composition are shown in Table 1.

[0161] [Comparative Example 5] (a+c(pt)) Non-hot melt organopolysiloxane resin fine particles (2) (vinyl group content = 0 mass%) 41.3 g, (a+c(pt)) 27.5 g of non-hot melt organopolysiloxane resin fine particles (1) (vinyl group content = 1.91% by mass), Formula (b4): ViMe2SiO(Me2SiO) 45 SiViMe2 27.5 g of dimethylpolysiloxane terminated at both molecular chain ends with dimethylvinylsiloxy groups (vinyl group content = 1.53% by mass), (c2(SiH)) formula: (HMeSiO 1 / 2 ) 0.67 (SiO 4 / 2 ) 0.33 Organohydrogenpolysiloxane resin (content of silicon-bonded hydrogen atoms = 0.95% by mass) {an amount such that the amount of silicon-bonded hydrogen atoms in the organohydrogenpolysiloxane resin is 1.0 mole per mole of vinyl groups in the organopolysiloxane resin fine particles (1) and the dimethylpolysiloxane terminally blocked with dimethylvinylsiloxy groups}, (d2) 299.0 g of titanium oxide having an average particle size of 0.5 μm (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.), (d3) 1.5 g of fumed silica having an average particle size of 0.04 μm (AEROSIL 50 manufactured by Nippon Aerosil Co., Ltd.), and 1-ethynyl-1-cyclohexanol (an amount equivalent to 1000 ppm by mass of the composition) were charged all at once into a small grinder and stirred for 1 minute at room temperature (25° C.) to prepare a uniform curable granular silicone composition. The results of measuring the softening point and other properties of this composition are shown in Table 1.

[0162] [Comparative Example 6] Average unit formula: (MeViSiO 2 / 2 ) 0.15 (MeSiO 2 / 2 ) 0.15 (Ph2SiO 2 / 2 ) 0.30 (PhSiO 3 / 2 ) 0.40 (HO 1 / 2 ) 0.04 55.2 g of methylvinylphenylpolysiloxane represented by the formula: (MeViSiO)4 13.8 g of 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane represented by the formula: (HMe2SiO)2SiPh2 30.9g of 1,1,5,5-tetramethyl-3,3-diphenyltrisiloxane represented by the formula (an amount such that the number of silicon-bonded hydrogen atoms in this component is 0.9 moles per mole of the total of vinyl groups in the methylvinylphenylpolysiloxane and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane), a 1,3-divinyl-1,1,3,3-tetramethyldisiloxane solution of platinum (an amount such that the platinum metal is 3.5 ppm by mass relative to the composition), 1-ethynyl-1-cyclohexanol (an amount such that the platinum metal is 200 ppm by mass relative to the composition), 55.2 g of titanium oxide (SX-3103 manufactured by Sakai Chemical Industry Co., Ltd.) having an average primary particle size of 0.2 μm, 74.6 g of crushed quartz powder (Crystallite VX-52 manufactured by Tatsumori Co., Ltd.) having an average particle size of 5 μm, and spherical silica (Nippon Steel Materials Co., Ltd.) having an average particle size of 15 μm. A paste-like curable silicone composition was prepared by mixing 60.8 g of HS-202 (Micron Corp.). The results of measurements of the softening point and other properties of this composition are shown in Table 1.

[0163] [Comparative Example 7] Hot melt silicone microparticles (1) 89.3 g, formula: HMe2SiO(Ph2SiO)SiMe2H 5.35 g of diphenylsiloxane terminated with dimethylhydrogensiloxy groups at both ends of the molecular chain (content of silicon-bonded hydrogen atoms = 0.6% by mass) with a viscosity of 5 mPa s, expressed as: (PhSiO 3 / 2 ) 0.4 (HMeSiO 1 / 2 ) 0.6 5.35 g of a branched-chain organopolysiloxane (content of silicon-bonded hydrogen atoms = 0.65 mass%) having two or more silicon-bonded hydrogen atoms in one molecule and a viscosity of 25 mPa·s {an amount in which the amount of silicon-bonded hydrogen atoms in the diphenylsiloxane and the branched-chain organopolysiloxane is 1.0 mole per mole of vinyl group in the silicone microparticles (1)}, 1-ethynyl-1-cyclohexanol (an amount in which the amount is 300 ppm by mass relative to the composition), and 402 g of spherical silica (HS-202 manufactured by Nippon Steel Materials Micron Co., Ltd.) having an average particle size of 15 μm were put into a small grinder at once and stirred for 1 minute at room temperature (25 ° C.) to prepare a uniform curable granular silicone composition. The results of the measurement of the softening point of this composition are shown in Table 1.

[0164] [Table 1]

[0165] [Summary] The curable silicone compositions of Examples 1 to 4 according to the present invention (hot-melt Examples 1 and 2, and paste-like Examples 3 and 4) satisfy the curing behavior (maximum torque value and loss tangent (tan δ) value) measured by the MDR specified in the present invention; they also have good moldability, allowing the molded product to be smoothly separated from the mold, and no warping of the molded product occurs, confirming that they have excellent stress relaxation properties.

[0166] On the other hand, Comparative Examples 1 to 7 did not satisfy the curing behavior measured by the MDR defined in the present invention, and there was a trade-off between moldability and suppression of warpage of the molded product (=low warpage), and it was not possible to achieve both.

Claims

1. A curable silicone composition for transfer molding, comprising: (A) a curable reactive organopolysiloxane; (B) a filler, and (C) containing a curing agent, (A1) 50 mass % or more of component (A) is an organopolysiloxane having a curing reactive functional group containing at least one carbon-carbon double bond in the molecule, and containing siloxane units selected from siloxane units represented by RSiO 3 / 2 (wherein R is a monovalent organic group) and siloxane units represented by SiO 4 / 2 , and the siloxane units account for at least 20 mol % of the total siloxane units; The content of the (B) component is 40 volume% or less of the entire composition, A curable silicone composition for transfer molding, which has (1) a maximum torque value of less than 50 dN·m as measured by a Moving Die Rheometer (MDR) at molding temperatures from room temperature to 200°C, and (2) a loss tangent (tan δ) value, expressed as the ratio of stored torque value / loss torque value, of less than 0.2 when the maximum torque value is reached.

2. 2. The curable silicone composition for transfer molding according to claim 1, wherein the composition as a whole has hot melt properties.

3. 3. The curable silicone composition for transfer molding according to claim 1, wherein component (A) is (A1-1) hot-melt organopolysiloxane fine particles having hydrosilylation reactive groups and / or radical reactive groups.

4. The component (A) is 1 ) resinous organopolysiloxane, (A 2 ) an organopolysiloxane crosslinked product obtained by partially crosslinking at least one organopolysiloxane; 3 3. The curable silicone composition for transfer molding according to claim 1 or 2, which is organopolysiloxane fine particles comprising a block copolymer consisting of a resinous organosiloxane block and a linear organosiloxane block, or a mixture of at least two of these.

5. The component (A) is R A SiO 3/2 (In the formula, R A 5. The curable silicone composition for transfer molding according to claim 1, which is an organopolysiloxane fine particle containing a siloxane unit represented by the formula:

6. 2. The curable silicone composition for transfer molding according to claim 1, wherein component (B) is one or more fillers selected from the group consisting of a reinforcing filler, a white pigment, a thermally conductive filler, and an electrically conductive filler.

7. The curable silicone composition for transfer molding according to any one of claims 1 to 6, which is in the form of pellets.

8. A cured product obtained by curing the curable silicone composition for transfer molding according to any one of claims 1 to 7.

9. Use of the cured product according to claim 8 as a member for a semiconductor device.

10. A semiconductor device comprising the cured product according to claim 8.

11. 11. The semiconductor device of claim 10, selected from a power semiconductor device, an optical semiconductor device, and a semiconductor device mounted on a flexible circuit board.

12. A method for producing a curable silicone composition for transfer molding according to any one of claims 1 to 7, characterized in that only the components constituting the curable silicone composition are mixed and granulated under temperature conditions not exceeding 50°C.

13. A method for molding a cured product comprising at least the following steps (I) to (III): (I) a step of heating the curable silicone composition for transfer molding according to any one of claims 1 to 7 to a temperature of 50°C or higher to melt it; (II) a step of injecting the liquid curable silicone composition obtained in step (I) into a mold, or a step of spreading the curable silicone composition obtained in step (I) throughout the mold by clamping the mold; and (III) A step of curing the curable silicone composition injected in the step (II)

14. 14. A method for molding a cured product according to claim 13, comprising a coating step of performing overmolding and underfilling of a semiconductor element at the same time with a cured product obtained by curing the curable silicone composition for transfer molding according to any one of claims 1 to 7.

15. 14. A method for molding a cured product according to claim 13, comprising a covering step of covering a surface of a semiconductor wafer substrate carrying one or more semiconductor elements with a cured product obtained by curing the curable silicone composition for transfer molding according to any one of claims 1 to 7, and overmolding the surface so that gaps between the semiconductor elements are filled with the cured product.

Citation Information

Patent Citations

  • Low-moisture permeable polyorganosiloxane composition

    JP2005008657A

  • Semiconductor device and manufacturing method thereof

    JP2005183788A

  • Flame-retardant adhesive polyorganosiloxane composition

    JP2006117845A

  • Polyorganosiloxane composition which gives transparent cured product

    JP2006335857A

  • White thermosetting silicone resin composition for optical semiconductor case, optical semiconductor case, and molding method therefor

    JP2009155415A